Acrylic resin modified silica particles, coating composition and multilayer coating film forming method

By using acrylic resin to modify silica particles, the problem of insufficient abrasion resistance and recoating adhesion of the coating film is solved, and high abrasion resistance and recoating adhesion of the coating film are achieved.

CN116829661BActive Publication Date: 2025-03-18KANSAI PAINT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180093212.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-08
Filing Date
2021-11-18
Publication Date
2025-03-18
Estimated Expiration
2041-11-18

AI Technical Summary

Technical Problem

The prior art has shortcomings in improving the abrasion resistance and recoating adhesion of the coating film, especially in the absence of adhesion during repeated coating.

Method used

The silica particles are modified with an acrylic resin, which are made of bonding silica particles having an average primary particle size of 5 to 100 nm and an acrylic resin selected from the group consisting of polyoxyalkylene chains and polyester chains.

Benefits of technology

The coating film has excellent abrasion resistance and recoating adhesion, ensuring high adhesion and durability of the coating film during repeated coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004381872510000341
    Figure BDA0004381872510000341
  • Figure BDA0004381872510000351
    Figure BDA0004381872510000351
  • Figure BDA0004381872510000381
    Figure BDA0004381872510000381
Patent Text Reader

Abstract

The present invention provides an acrylic resin-modified silica particle, which, when used in a coating composition, can be used to form a coating composition that has excellent scratch resistance and excellent adhesion during repeated coating (recoating adhesion). The acrylic resin-modified silica particle comprises a silica particle (A) and an acrylic resin (B) bonded to the silica particle (A), wherein the acrylic resin (B) has at least one chain selected from a polyoxyalkylene chain and a polyester chain and a polysiloxane structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to acrylic resin-modified silica particles, a coating composition using the acrylic resin-modified silica particles, and a method for forming a multilayer coating film. Background Art

[0002] For coatings applied to objects such as automobile bodies, the coating film is required to have excellent appearance and excellent coating film performance such as scratch resistance. As a method for meeting such requirements, the following technology has been developed: chemically modified silica particles are added to the coating composition to improve the scratch resistance of the formed coating film.

[0003] For example, Patent Document 1 discloses a coating composition characterized by containing silica particles (A) whose surfaces are modified with a specific hydrolyzable silane compound (a) and a binder component (B).

[0004] In addition, Patent Document 2 discloses a coating composition characterized in that it contains: (A) a hydroxyl-containing acrylic resin, which is a copolymer of monomer components consisting of (a) 25 to 50% by mass of a hydroxyl-containing polymerizable unsaturated monomer, (b) 5 to 30% by mass of a polymerizable unsaturated monomer containing an alicyclic hydrocarbon group having 6 to 20 carbon atoms, and (c) 20 to 70% by mass of other polymerizable unsaturated monomers; (B) a polyisocyanate compound, which is composed of an aliphatic diisocyanate having an isocyanurate trimer content of 30 to 70% by mass, a uretdione dimer content of 3 to 30% by mass, and a polymer content of other trimers or higher of 0 to 67% by mass, based on the total amount of the polyisocyanate compound; and (C) polysiloxane-modified silica particles having an average primary particle size of 1 to 40 nm.

[0005] According to these prior arts, the obtained cured coating film can be given excellent properties such as scratch resistance. However, if the properties of modified silica are designed in a manner that can form a coating surface with excellent scratch resistance, sufficient properties may not be obtained in the adhesion (recoat adhesion) during repeated coating.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2013-249400

[0009] Patent Document 2: Japanese Patent Application Publication No. 2013-53305 Summary of the invention

[0010] Problem that the invention aims to solve

[0011] The present invention relates to acrylic resin-modified silica particles, which, when used in a coating composition, can form a coating composition that has excellent scratch resistance and excellent adhesion (recoat adhesion) when repeatedly coated. In addition, the present invention also relates to a coating composition containing the acrylic resin-modified silica particles and a method for forming a multilayer coating film.

[0012] Technical Solution

[0013] The present invention includes the following aspects.

[0014] [Item 1]

[0015] An acrylic resin-modified silica particle comprises silica particles (A) and an acrylic resin (B) bonded to the silica particles (A), wherein the acrylic resin (B) has a polysiloxane structure and at least one chain selected from a polyoxyalkylene chain and a polyester chain.

[0016] [Item 2]

[0017] The acrylic resin-modified silica particles according to item 1, wherein the silica particles (A) are colloidal silica having an average primary particle size of 5 to 100 nm.

[0018] [Item 3]

[0019] The acrylic resin-modified silica particles according to item 1 or 2, wherein the acrylic resin-modified silica particles are a reaction product of silica particles (a1) and a compound (a2), wherein the silica particles (a1) are bonded to an acrylic resin having a first chemically reactive group; and the compound (a2) has a second chemically reactive group capable of reacting with the first chemically reactive group, at least one chain selected from a polyoxyalkylene chain and a polyester chain, and a polysiloxane structure.

[0020] [Item 4]

[0021] The acrylic resin-modified silica particles according to item 3, wherein the silica particles (a1) bonded to the acrylic resin having a first chemically reactive group are a reaction product of silica particles (a11) having a polymerizable unsaturated group and a polymerizable unsaturated monomer mixture (a12), wherein the polymerizable unsaturated monomer mixture (a12) contains a polymerizable unsaturated monomer (a121) having a first chemically reactive group as at least a part of its components.

[0022] [Item 5]

[0023] The acrylic resin-modified silica particles according to item 4, wherein the polymerizable unsaturated monomer (a121) having a first chemically reactive group is at least one polymerizable unsaturated monomer selected from a carboxyl group-containing polymerizable unsaturated monomer, an epoxy group-containing polymerizable unsaturated monomer, an isocyanate group-containing polymerizable unsaturated monomer, and an amino group-containing polymerizable unsaturated monomer.

[0024] [Item 6]

[0025] The acrylic resin-modified silica particles according to any one of items 3 to 5, wherein the compound (a2) having a second chemically reactive group capable of reacting with the first chemically reactive group, at least one chain selected from a polyoxyalkylene chain and a polyester chain, and a polysiloxane structure is a compound having at least one chemically reactive group selected from an epoxy group, a carboxyl group, an amino group, a hydroxyl group, and an isocyanate group as the second chemically reactive group.

[0026] [Item 7]

[0027] The acrylic resin-modified silica particles according to any one of items 3 to 6, wherein the number average molecular weight of the compound (a2) having a second chemically reactive group capable of reacting with the first chemically reactive group, at least one chain selected from a polyoxyalkylene chain and a polyester chain, and a polysiloxane structure is within a range of 200 to 4000.

[0028] [Item 8]

[0029] The acrylic resin-modified silica particles according to any one of items 3 to 7, wherein the mass ratio of the silica particles (a1) to the compound (a2) is in the range of (a1) / (a2)=90 / 10 to 98 / 2, the compound (a2) has a second chemically reactive group capable of reacting with the first chemically reactive group, at least one chain selected from a polyoxyalkylene chain and a polyester chain, and a polysiloxane structure, and the silica particles (a1) are bonded to the acrylic resin having the first chemically reactive group.

[0030] [Item 9]

[0031] The acrylic resin-modified silica particles according to any one of items 1 to 8, wherein the acrylic resin (B) having a polysiloxane structure and at least one chain selected from a polyoxyalkylene chain and a polyester chain is an acrylic resin (B′) further having a hydroxyl group.

[0032] [Item 10]

[0033] The acrylic resin-modified silica particles according to item 4, wherein the acrylic resin (B) having at least one chain selected from a polyoxyalkylene chain and a polyester chain and a polysiloxane structure is an acrylic resin (B') further having a hydroxyl group, and the hydroxyl value of the acrylic resin produced from the polymerizable unsaturated monomer mixture (a12) is in the range of 60 to 140 mgKOH / g.

[0034] [Item 11]

[0035] The acrylic resin-modified silica particles according to any one of items 1 to 10, wherein, in the acrylic resin-modified silica particles, the mass ratio of the polysiloxane structure to the at least one chain selected from the polyoxyalkylene chain and the polyester chain is in the range of 65 / 35 to 5 / 95 in terms of the mass ratio of (polysiloxane structure) / (at least one chain selected from the polyoxyalkylene chain and the polyester chain).

[0036] [Item 12]

[0037] A coating composition comprising the acrylic resin-modified silica particles according to any one of items 1 to 11 and a binder component.

[0038] [Item 13]

[0039] The coating composition according to item 12, wherein the binder component comprises a hydroxyl-containing resin and a crosslinking agent.

[0040] [Item 14]

[0041] A method for forming a multi-layer coating film, which is a method for forming a multi-layer coating film by sequentially applying at least one layer of colored base coating paint and at least one layer of clear coating paint on a coated object, wherein the method includes the step of applying the coating composition described in item 12 or 13 as the topmost clear coating paint.

[0042] Beneficial Effects

[0043] According to the acrylic resin-modified silica particles of the present invention, when blended in a coating composition, a coating composition capable of forming a coating film having excellent scratch resistance and excellent adhesion during repeated coating (recoat adhesion) can be obtained. DETAILED DESCRIPTION

[0044] Hereinafter, the present invention will be described in detail.

[0045] The acrylic resin-modified silica particles of the present invention are modified silica particles comprising silica particles (A) and an acrylic resin (B) bonded to the silica particles (A), wherein the acrylic resin (B) has at least one chain selected from a polyoxyalkylene chain and a polyester chain and has a polysiloxane structure.

[0046] Silica particles (A)

[0047] As the silica particles (A) used to form the acrylic resin modified silica particles of the present invention, any silica particles that can form a bond with the acrylic resin can be used without particular limitation. Such silica particles include, for example, dry silica, wet silica, silica gel, calcium ion exchange silica particles, colloidal silica, etc., and colloidal silica that is silica particles having hydroxyl groups and / or alkoxy groups on the particle surface and dispersed in a dispersion medium is particularly preferred.

[0048] As the above-mentioned dispersion medium, for example, water; alcohol solvents such as methanol, ethanol, isopropanol, n-propanol, isobutanol, and n-butanol; polyol solvents such as ethylene glycol; polyol derivatives such as ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, and propylene glycol monomethyl ether; ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone, and diacetone alcohol, etc. As the above-mentioned dispersion medium, a lower alcohol solvent or a lower polyol derivative having a carbon number of 3 or less is preferred. The reason is that it is easy to remove by the solvent removal step in the manufacture of the silica particles (a11) having a polymerizable unsaturated group described later.

[0049] Examples of colloidal silica include methanol silica sol, IPA-ST, MEK-ST, NBA-ST, XBA-ST, DMAC-ST, PGM-ST, ST-UP, ST-OUP, ST-20, ST-40, ST-C, ST-N, ST-O, ST-50, and ST-OL (all manufactured by Nissan Chemical Industries, Ltd.).

[0050] The average primary particle size of the raw silica particles is preferably 5 to 100 nm, more preferably 5 to 50 nm. If the average primary particle size is less than 5 nm, when the dispersion is mixed with other organic materials, the improvement effect of mechanical properties is sometimes reduced. If the average primary particle size exceeds 100 nm, transparency is sometimes impaired.

[0051] In this specification, "average primary particle size" refers to the median particle size (d50) of the volume-based particle size distribution, and the volume-based particle size distribution is measured by a laser diffraction / scattering method. In the present invention, the volume-based particle size distribution of the dispersion is measured using a laser diffraction / scattering particle size distribution measuring device "Microtrac MT3300" (trade name, manufactured by Nikkiso Co., Ltd.). At this time, the sample concentration is adjusted to the range of the specified transmittance set in the device.

[0052] The acrylic resin-modified silica particles of the present invention have a structure in which silica particles (A) are chemically bonded to an acrylic resin (B) having at least one chain selected from a polyoxyalkylene chain and a polyester chain and a polysiloxane structure. The method for forming such a structure is not particularly limited.

[0053] As one specific method for forming a structure in which silica particles (A) are chemically bonded to an acrylic resin (B) having at least one chain selected from a polyoxyalkylene chain and a polyester chain and a polysiloxane structure, for example, the following method can be mentioned: first, silica particles (a11) having a polymerizable unsaturated group are reacted with a polymerizable unsaturated monomer mixture (a12) containing a polymerizable unsaturated monomer (a121) having a first chemically reactive group to obtain silica particles (a1) bonded to an acrylic resin having a first chemically reactive group; then, the silica particles (a1) bonded to an acrylic resin having a first chemically reactive group are reacted with a compound (a2) having a second chemically reactive group, at least one chain selected from a polyoxyalkylene chain and a polyester chain, and a polysiloxane structure, thereby introducing at least one chain selected from a polyoxyalkylene chain and a polyester chain and a polysiloxane structure into the acrylic resin portion of the silica particles (a1) bonded to the acrylic resin having a first chemically reactive group. Here, the first chemically reactive group and the second chemically reactive group can be selected from a combination of any chemically reactive groups that can form a chemical bond by reaction, and the details are described later. In addition, a polymerizable unsaturated group refers to an unsaturated group that can undergo free radical polymerization. Examples of such polymerizable unsaturated groups include vinyl, (meth)acryloyl, (meth)allyl, etc., but are not limited to these. Here, "(meth)acryloyl" refers to acryloyl or methacryloyl, and "(meth)allyl" refers to allyl or methallyl.

[0054] The above-mentioned specific method scheme is described in further detail.

[0055] When the above-mentioned specific method is used, first, the silica particles (a11) having a polymerizable unsaturated group are reacted with the polymerizable unsaturated monomer mixture (a12) containing the polymerizable unsaturated monomer (a121) having a first chemically reactive group to obtain the silica particles (a1) bonded to the acrylic resin having the first chemically reactive group. This point will be described below.

[0056] Silica particles having polymerizable unsaturated groups (a11)

[0057] As the silica particles (a11) having a polymerizable unsaturated group, for example, silica particles having a polymerizable unsaturated group obtained by mixing and heating raw silica particles, an organic solvent, and a monomer having a polymerizable unsaturated group and a hydrolyzable silyl group can be used. In addition, a particle obtained by further adding a tertiary amine to the silica particles (a11) having a polymerizable unsaturated group can also be used.

[0058] The organic solvent is preferably a hydrophilic organic solvent. Examples of the hydrophilic organic solvent include: alcohol organic solvents such as methanol, ethanol, isopropanol, n-butanol, and isobutanol; ether organic solvents such as dioxane and tetrahydrofuran; ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-n-propyl ether, ethylene glycol monoisopropyl ether, ethylene glycol mono-n-butyl ether, ethylene glycol monoisobutyl ether, ethylene glycol mono-tert-butyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol mono-n-propyl ether, diethylene glycol mono-tert-butyl ether, Glycol ether organic solvents such as monoisopropyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol monoisobutyl ether, diethylene glycol mono-tert-butyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono-n-propyl ether, propylene glycol monoisopropyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol mono-n-propyl ether, and dipropylene glycol monoisopropyl ether; ester organic solvents such as ethyl acetate, butyl acetate, isobutyl acetate, and 3-methoxybutyl acetate, etc., which can be used alone or in combination of two or more.

[0059] As the organic solvent, alcohols and / or glycol ethers are preferred. Among them, alcohols having a boiling point of 64 to 132° C., particularly 82 to 118° C., and glycol ethers having a boiling point of 120 to 208° C., particularly 120 to 192° C. are more preferred, and alcohols having 2 to 8 carbon atoms, particularly 3 to 5 carbon atoms, and glycol ethers having 3 to 5 carbon atoms, particularly 3 to 4 carbon atoms are further preferred.

[0060] Examples of the monomer having a polymerizable unsaturated group and a hydrolyzable silyl group include 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 2-(meth)acryloxyethyltrimethoxysilane, 2-(meth)acryloxyethyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 2-(meth)acryloxyethylmethyldimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, allyltrimethoxysilane, allyltriethoxysilane, and monomers having a polymerizable unsaturated group and a hydrolyzable silyl group obtained by reaction of functional groups other than the hydrolyzable silyl group possessed by various silane coupling agents with functional groups other than the unsaturated group of an unsaturated compound.

[0061] The silica particles (a11) having a polymerizable unsaturated group are obtained by heating and mixing raw silica particles, an organic solvent, and a monomer having a polymerizable unsaturated group and a hydrolyzable silyl group. In more detail, it can be manufactured by mixing raw silica particles, an organic solvent, and a monomer having a polymerizable unsaturated group and a hydrolyzable silyl group dispersed in a dispersion medium, and azeotropically distilling the organic solvent and the dispersion medium of the silica particles (including a lower alcohol produced by hydrolyzing the monomer having a polymerizable unsaturated group and a hydrolyzable silyl group) from the mixture under normal pressure or reduced pressure, and performing a dehydration condensation reaction under heating while replacing the dispersion medium with the above-mentioned organic solvent or after replacing it with the above-mentioned organic solvent.

[0062] The non-volatile component concentration of the dispersion during the reaction is preferably in the range of about 5 to about 50 mass %. If the non-volatile component concentration is less than about 5 mass %, that is, the solvent exceeds about 95 mass %, the reaction time of the silica particles and the monomer having a polymerizable unsaturated group and a hydrolyzable silyl group may be prolonged, and the production efficiency may be reduced. On the other hand, if the non-volatile component concentration exceeds about 50 mass %, the product may gel.

[0063] By these production methods, silicon atoms on the surfaces of the raw silica particles are bonded to silicon atoms of the monomer having a polymerizable unsaturated group and a hydrolyzable silyl group via oxygen atoms to form siloxane bonds, thereby obtaining a dispersion of silica particles (a11) having a polymerizable unsaturated group in which the silica particles and the monomer having a polymerizable unsaturated group and a hydrolyzable silyl group are chemically bonded.

[0064] The mixing ratio of the monomer having a polymerizable unsaturated group and a hydrolyzable silyl group when obtaining the silica particles (a11) having a polymerizable unsaturated group is preferably about 0.2 to about 95 parts by mass relative to 100 parts by mass of the silica particles, more preferably about 0.5 to about 50 parts by mass, and further preferably about 1.0 to about 20 parts by mass. If the ratio of the monomer having a polymerizable unsaturated group and a hydrolyzable silyl group is less than about 0.2 parts by mass, the silica particles (a) having a polymerizable unsaturated group generated sometimes have poor stability in the dispersion medium. If the ratio of the monomer having a polymerizable unsaturated group and a hydrolyzable silyl group is more than about 95 parts by mass, sometimes in the reaction with the raw silica particles, the monomer having a polymerizable unsaturated group and a hydrolyzable silyl group remains in an unreacted state.

[0065] In addition, in the case of obtaining silica particles (a11) with polymerizable unsaturated groups, it is also possible to react the alkoxysilane with an alkyl group having more than 1 carbon atoms with the monomer and the raw silica particles having polymerizable unsaturated groups and hydrolyzable silyl groups as needed. By reacting the alkoxysilane with an alkyl group having more than 1 carbon atoms, the water resistance of the obtained coating film can be improved sometimes. As the alkoxysilane with an alkyl group having more than 1 carbon atoms, for example, methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, butyltrimethoxysilane, hexyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, etc., compounds (such as methyltriethoxysilane, etc.) in which the methoxy groups in the compounds shown by way of example are substituted with ethoxy groups can also be listed.

[0066] As the silica particles (a11) having a polymerizable unsaturated group, from the viewpoint of storage stability, scratch resistance, and the like, silica particles (a11) having a polymerizable unsaturated group to which a tertiary amine is added can be used.

[0067] The tertiary amine can be used without particular limitation as long as it has a molecular weight of 120 to 380, preferably 130 to 350, more preferably 150 to 300 and has an alkyl group and / or an aryl group at the end. As the tertiary amine, from the viewpoints of storage properties and scratch resistance, it is preferred that at least one of the alkyl groups possessed by the tertiary amine is an alkyl group having 3 or more carbon atoms, preferably 4 to 12, more preferably 5 to 10 carbon atoms. Among them, from the viewpoints of storage properties and scratch resistance, it is particularly preferred that at least one of the alkyl groups possessed by the tertiary amine is a linear alkyl group.

[0068] Examples of the tertiary amine include straight-chain tertiary amines such as tripropylamine, tributylamine, tri-n-pentylamine, tri-n-hexylamine, tri-n-heptylamine, and tri-n-octylamine; branched-chain tertiary amines such as triisopropylamine, triisobutylamine, and tri-2-ethylhexylamine; tertiary amines having mixed hydrocarbon groups such as dimethyloctylamine, dimethyldodecylamine, dimethyloctadecylamine, hexyldiethylamine, octyldiethylamine, and diethyldodecylamine; alicyclic tertiary amines such as dimethylcyclohexylamine and tricyclohexylamine; tertiary amines having aromatic ring substituents such as dimethylbenzylamine and tribenzylamine; etc. These may be used alone or in combination of two or more.

[0069] As a method for adding the above-mentioned tertiary amine to the silica particles (a11) having a polymerizable unsaturated group, a conventionally known method can be used. As the amount of the above-mentioned tertiary amine used, from the viewpoints of storage stability and the scratch resistance of the coating film obtained when it is combined with the coating, it is preferably 0.1 to 5.0 parts by mass, preferably 1.5 to 3.0 parts by mass, and more preferably 1.7 to 2.5 parts by mass based on 100 parts by mass of the solid content of the silica particles (a11) having a polymerizable unsaturated group.

[0070] The silica particles (a11) having a polymerizable unsaturated group obtained above are reacted with a polymerizable unsaturated monomer mixture (a12) containing the polymerizable unsaturated monomer (a121) having a first chemically reactive group as a part of its components, thereby obtaining silica particles (a1) bonded to an acrylic resin having a first chemically reactive group. The polymerizable unsaturated monomer mixture (a12) is described below.

[0071] Polymerizable unsaturated monomer mixture (a12)

[0072] The polymerizable unsaturated monomer mixture (a12) to be used for the reaction with the silica particles (a11) having a polymerizable unsaturated group contains, as at least part of its components, a polymerizable unsaturated monomer (a121) having a first chemically reactive group.

[0073] The polymerizable unsaturated monomer (a121) having a first chemically reactive group is a polymerizable unsaturated monomer having a chemically reactive group that can react with a second chemically reactive group of the compound (a2) described later.

[0074] As the combination of the first chemically reactive group in the above-mentioned polymerizable unsaturated monomer (a121) and the second chemically reactive group in the compound (a2), according to the combination of the first chemically reactive group / the second chemically reactive group, for example, there can be listed: epoxy / carboxyl, carboxyl / epoxy, hydroxyl / isocyanate, isocyanate / hydroxyl, hydroxyl / alkoxysilyl, alkoxysilyl / hydroxyl, amino / isocyanate, isocyanate / amino, epoxy / amino, amino / epoxy, etc. Among them, any combination of epoxy / carboxyl, carboxyl / epoxy, hydroxyl / isocyanate, or epoxy / amino is preferred, and the combination of carboxyl / epoxy is particularly preferred.

[0075] More specifically, the combination of the polymerizable unsaturated monomer (a121) having a first chemically reactive group and the compound (a2) having a second chemically reactive group is preferably any of the following combinations, among which the following combination (i) is particularly preferred.

[0076] (i) The polymerizable unsaturated monomer (a121) having a first chemically reactive group is a polymerizable unsaturated monomer containing a carboxyl group, and the compound (a2) having a second chemically reactive group is a compound containing an epoxy group; (ii) The polymerizable unsaturated monomer (a121) having a first chemically reactive group is a polymerizable unsaturated monomer containing an epoxy group, and the compound (a2) having a second chemically reactive group is a compound containing a carboxyl group; (iii) The polymerizable unsaturated monomer (a121) having a first chemically reactive group is a polymerizable unsaturated monomer containing a hydroxyl group, and the compound (a2) having a second chemically reactive group is an isocyanate group-containing compound.

[0077] As the polymerizable unsaturated monomer containing epoxy group, for example, there can be listed: glycidyl (meth)acrylate, β-methyl glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, 3,4-epoxycyclohexylethyl (meth)acrylate, 3,4-epoxycyclohexylpropyl (meth)acrylate, allyl glycidyl ether, etc., which can be used alone or in combination of two or more. Among them, glycidyl methacrylate can be preferably used. It should be noted that in this specification, "(meth)acrylate" refers to "acrylate or methacrylate". "(Meth)acrylic acid" refers to "acrylic acid or methacrylic acid". In addition, "(meth)acrylamide" refers to "acrylamide or methacrylamide".

[0078] Examples of the carboxyl-containing polymerizable unsaturated monomer include (meth)acrylic acid, maleic acid, crotonic acid, itaconic acid, and β-carboxyethyl acrylate, and these can be used alone or in combination of two or more. Among them, acrylic acid and / or methacrylic acid can be preferably used.

[0079] Examples of the hydroxyl-containing polymerizable unsaturated monomer include: monoesters of (meth)acrylic acid and a diol having 2 to 8 carbon atoms, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; and ε-caprolactone-modified monoesters of (meth)acrylic acid and a diol having 2 to 8 carbon atoms, and the like, which can be used alone or in combination of two or more. Among them, 2-hydroxyethyl acrylate and / or 2-hydroxyethyl methacrylate can be preferably used.

[0080] As the polymerizable unsaturated monomer containing isocyanate group, for example, 2-isocyanate (meth) ethyl acrylate, m-isopropenyl-α, α-dimethylbenzyl isocyanate, etc. can be listed. In addition, as the commercially available product of the polymerizable unsaturated monomer containing isocyanate group, for example, "Karenz MOI", "Karenz AOI", "Karenz MOI-EG" (the above are made by Showa Denko K.K.) and the like can be listed. In addition, the above-mentioned polymerizable unsaturated monomer containing isocyanate group can be used alone or in combination of two or more. Among them, 2-isocyanate ethyl acrylate and / or 2-isocyanate ethyl methacrylate can be preferably used.

[0081] Examples of the amino group-containing polymerizable unsaturated monomer include dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, diethylaminoethyl acrylate, diethylaminoethyl methacrylate, dimethylaminopropyl acrylamide, and dimethylaminopropyl methacrylamide.

[0082] Examples of the polymerizable unsaturated monomer containing an alkoxysilyl group include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltripropoxysilane, vinyltributoxysilane, (meth)acryloxymethyltrimethoxysilane, (meth)acryloxyethyltrimethoxysilane, γ-(meth)acryloxypropyltrimethoxysilane, γ-(meth)acryloxypropyltriethoxysilane, (meth)acryloxyethyltriethoxysilane, (meth)acryloxypropyltributoxysilane, vinyltriβ-methoxyethoxysilane, divinylmethoxysilane, and divinyldiβ-methoxyethoxysilane.

[0083] The polymerizable unsaturated monomer mixture (a12) may contain other polymerizable unsaturated monomers other than the polymerizable unsaturated monomer (a121) having the first chemically reactive group. Examples of other polymerizable unsaturated monomers include: C1 to C24 alkyl or cycloalkyl esters of (meth)acrylic acid such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, and cyclohexyl (meth)acrylate; C1 to C16 alkoxyalkyl esters of (meth)acrylic acid such as methoxybutyl acrylate, methoxybutyl methacrylate, methoxyethyl acrylate, methoxyethyl methacrylate, ethoxybutyl acrylate, ethoxybutyl methacrylate, and phenoxyethyl (meth)acrylate; (meth)acrylates having a polyoxyalkylene chain; (Meth)acrylates; (meth)acrylates having a polysiloxane structure; aromatic unsaturated monomers such as styrene, vinyltoluene, α-methylstyrene, N-vinylpyrrolidone, and vinylpyridine; olefins such as ethylene, propylene, butene, and pentene; diene compounds such as butadiene, isoprene, and chloroprene; cyclohexenyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, N-butoxy (meth)acrylamide, adducts of glycidyl (meth)acrylate and amines, vinyl propionate, vinyl acetate, vinyl pivalate, VeoVa Monomer (a product of Shell Chemical Company), and the like.

[0084] Even the epoxy-containing polymerizable unsaturated monomer, carboxyl-containing polymerizable unsaturated monomer, hydroxyl-containing polymerizable unsaturated monomer, isocyanate-containing polymerizable unsaturated monomer, etc., which are exemplified in the description of the polymerizable unsaturated monomer (a121) having the first chemically reactive group, can be used as the above-mentioned other polymerizable unsaturated monomers if they are polymerizable unsaturated monomers that do not have reactivity with the second chemically reactive group possessed by the compound (a2) described later.

[0085] In the present invention, the acrylic resin (B) having at least one chain selected from polyoxyalkylene chains and polyester chains and a polysiloxane structure is preferably an acrylic resin (B') further having a hydroxyl group from the viewpoint of the scratch resistance and recoatability of the formed coating film.

[0086] The above-mentioned acrylic resin (B') having a hydroxyl group can be obtained, for example, by containing a hydroxyl-containing polymerizable unsaturated monomer as a constituent component of a polymerizable unsaturated monomer mixture (a12). As the hydroxyl-containing polymerizable unsaturated monomer, the hydroxyl-containing polymerizable unsaturated monomer exemplified in the description of the polymerizable unsaturated monomer (a121) having a first chemically reactive group can be used. In addition, from the viewpoints of the scratch resistance and recoating adhesion of the formed coating film, the hydroxyl value of the acrylic resin manufactured from the polymerizable unsaturated monomer mixture (a12) is preferably in the range of 60 to 140, more preferably in the range of 65 to 130, and even more preferably in the range of 70 to 120.

[0087] When the polymerizable unsaturated monomer mixture (a12) contains other polymerizable unsaturated monomers other than the polymerizable unsaturated monomer (a121) having the first chemically reactive group, the content of the other polymerizable unsaturated monomers is preferably 99.5% by mass or less, and more preferably 99% by mass or less, based on the total mass of the polymerizable unsaturated monomer mixture (a12).

[0088] Formation of silica particles (a1) bonded to acrylic resin having a first chemically reactive group

[0089] The silica particles (a1) bonded to the acrylic resin having the first chemically reactive group can be obtained by subjecting the silica particles (a11) having the polymerizable unsaturated group to polymerization reaction with the polymerizable unsaturated monomer mixture (a12) in the presence of a solvent. The polymerization method is not particularly limited, and a known polymerization method can be used, among which a solution polymerization method in which polymerization is carried out in an organic solvent in the presence of a catalyst, a polymerization initiator, etc. can be preferably used.

[0090] Examples of the organic solvent used in the solution polymerization method include aromatic compounds such as benzene, toluene, xylene, ethylbenzene, "Swazol 1000", "Swazol 1500" (trade name, manufactured by Maruzen Petrochemical Co., Ltd., high boiling point petroleum solvents); pentane, hexane, heptane, octane, cyclohexane, cycloheptane, mineral spirits; spirit) and other hydrocarbon solvents; halogenated hydrocarbons such as trichloroethylene and tetrachloroethylene; ester solvents such as ethyl acetate, n-butyl acetate, isobutyl acetate, ethyl propionate, methyl cellosolve acetate, butyl carbitol acetate, ethylene glycol monomethyl ether acetate, diethylene glycol monobutyl ether acetate, and 3-ethoxypropionate; ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone, diisobutyl ketone, and cyclohexanone; alcohol solvents such as methanol, ethanol, isopropanol, n-butanol, sec-butanol, isobutanol, ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and ethylene glycol monobutyl ether; ether solvents such as n-butyl ether, dioxane, dibutyl ether, and ethylene glycol dimethyl ether; dimethyl sulfoxide, dimethylformamide, N-methylpyrrolidone, or water. These organic solvents can be used alone or in combination of two or more. Among them, from the perspective of the appearance of the formed coating film, aromatic solvents and ester solvents are preferred, and ester solvents are further preferred.

[0091] The polymerization initiator that can be used in the above-mentioned polymerization is not particularly limited, and examples thereof include benzoyl peroxide, p-menthane hydroperoxide, cumene hydroperoxide, lauroyl peroxide, cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, methylcyclohexanone peroxide, tert-butyl peroxypivalate, 1,1'-bis(tert-butylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, n-butyl 4,4-bis(tert-butylperoxy)valerate, 2,2'-di(tert-butylperoxy)butyl 1,3-bis(tert-butylperoxy-m-isopropyl)benzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, diisopropyl peroxide, tert-butylcumyl peroxide, decanoyl peroxide, lauroyl peroxide, benzoyl peroxide, 2,4-dichlorobenzoyl peroxide, bis(tert-butylcyclohexyl) peroxydicarbonate, benzene peroxide Peroxide polymerization initiators such as tert-butyl formate, 2,5-dimethyl-2,5-di(benzoyl peroxide)hexane, and hydrogen peroxide; 1,1-azobis(cyclohexane-1-carbonitrile), azoisopropylbenzene, 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobisisobutyronitrile, 2,2'-azobis-(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 2,2'-bis(2-hydroxyethyl)azobisisobutylene Azo polymerization initiators such as butyronitrile, 4,4'-azobis(4-cyanovaleric acid), 2-(tert-butylazo)-2-cyanopropane, 2,2'-azobis(2,4,4-trimethylpentane), 2,2'-azobis(2-methylpropane), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 2,2'-azobis-(N-butyl-2-methylpropionamide); persulfate initiators such as potassium persulfate and sodium persulfate; and free radical polymerization initiators known per se such as redox initiators containing a peroxide and a reducing agent.

[0092] The amount of the free radical polymerization initiator used is preferably 0.1 to 20 parts by mass, particularly preferably 1 to 10 parts by mass, relative to 100 parts by mass of the polymerizable unsaturated monomer mixture (a12). If the free radical polymerization initiator is less than 0.1 parts by mass, the proportion of unreacted polymerizable unsaturated monomers that do not react with the silica particles (a11) having a polymerizable unsaturated group may increase. If the free radical polymerization initiator is more than 20 parts by mass, the aggregation of particles may occur due to the polymerization of the silica particles bonded with the acrylic resin.

[0093] In the case of reacting the silica particles (a11) having a polymerizable unsaturated group with a polymerizable unsaturated monomer mixture (a12) in a solvent, the total mass concentration of the silica particles (a11) having a polymerizable unsaturated group and the polymerizable unsaturated monomer mixture (a12) is preferably about 10% by mass to about 90% by mass, and is particularly preferably in the range of about 20% by mass to about 70% by mass. If the above-mentioned total mass concentration is less than about 10% by mass, the reaction time sometimes becomes longer and the manufacturing efficiency decreases. If the above-mentioned total mass concentration is higher than about 90% by mass, the viscosity of the reaction system sometimes becomes higher and becomes difficult to stir.

[0094] From the viewpoint of suppressing the polymerization reaction hindrance caused by oxygen and improving the reaction rate, the reaction is preferably carried out while stirring while replacing the gas phase in the reaction container with an inert gas. The reaction temperature and reaction time can be appropriately selected according to the type of the polymerizable unsaturated monomer mixture (a12), and the reaction temperature is preferably in the range of about 0°C to about 250°C, and the reaction time is preferably in the range of 1 to 72 hours. The reaction can usually be carried out under normal pressure, but can also be carried out under pressure or reduced pressure.

[0095] The polymerization rate of the polymerizable unsaturated monomer mixture (a12) in the above reaction is preferably about 90% or more, particularly preferably about 95% or more. When the polymerization rate of the polymerizable unsaturated monomer mixture (a12) is less than about 90%, the coating properties such as scratch resistance are sometimes poor. The amount of unreacted polymerizable unsaturated monomer mixture (a12) can be reduced by extending the reaction time. When the unreacted polymerizable unsaturated monomer mixture (a12) is a small amount, it can be reduced by adding a free radical polymerization initiator to further proceed the polymerization reaction.

[0096] A compound (a2) having a second chemically reactive group, at least one chain selected from a polyoxyalkylene chain and a polyester chain, and a polysiloxane structure

[0097] The acrylic resin modified silica particles of the present invention can be obtained by reacting silica particles (a1) bonded to an acrylic resin having a first chemically reactive group with a compound (a2) having a second chemically reactive group, at least one chain selected from a polyoxyalkylene chain and a polyester chain, and a polysiloxane structure. Examples of the compound (a2) to be reacted with the silica particles (a1) include modified organic silicon compounds modified with a chemically reactive group and at least one chain selected from a polyoxyalkylene chain and a polyester chain. Here, the chemically reactive group is selected from chemically reactive groups (second chemically reactive groups) having reactivity with the first chemically reactive group.

[0098] Examples of such modified silicone compounds include those obtained by introducing a chemically reactive group (second chemically reactive group) and at least one chain selected from a polyoxyalkylene chain and a polyester chain into a side chain and / or terminal of a compound having a polysiloxane structure such as dimethylpolysiloxane.

[0099] Examples of compounds having a polysiloxane structure include dialkyl silicone, alkyl aryl silicone, and diaryl silicone. The alkyl group in the structural unit of these silicones is preferably an alkyl group having 1 to 6 carbon atoms. In addition, phenyl and naphthyl groups are included, preferably phenyl groups. Examples of dialkyl silicone, alkyl aryl silicone, and diaryl silicone include dimethyl silicone, methylphenyl silicone, and diphenyl silicone.

[0100] As the chemically reactive group (second chemically reactive group) introduced into the side chain and / or the terminal of the compound having a polysiloxane structure, the chemically reactive groups exemplified in the description of the polymerizable unsaturated monomer (a121) having a first chemically reactive group, i.e., the combination of the first chemically reactive group / the second chemically reactive group, can be listed: epoxy / carboxyl, carboxyl / epoxy, hydroxyl / isocyanate, isocyanate / hydroxyl, hydroxyl / alkoxysilyl, alkoxysilyl / hydroxyl, amino / isocyanate, isocyanate / amino, epoxy / amino, amino / epoxy, etc. Among them, any combination of epoxy / carboxyl, carboxyl / epoxy, hydroxyl / isocyanate, or epoxy / amino is preferred, and the combination of carboxyl / epoxy is particularly preferred.

[0101] In addition, as the polyoxyalkylene chain introduced into the side chain and / or the terminal of the compound having a polysiloxane structure, for example, there can be listed: polyoxyalkylene chains containing alkylene structures having 2 to 4 carbon atoms, such as polyoxyethylene chains, polyoxypropylene chains, polyoxybutylene chains, and polyoxyethylenepolyoxypropylene chains. Among them, polyoxyethylene chains, polyoxypropylene chains, and polyoxyethylenepolyoxypropylene chains are preferred, and polyoxyethylenepolyoxypropylene chains are particularly preferred. Here, the polyoxyethylenepolyoxypropylene chain is an organic residue formed by a copolymerization structure of an oxyethylene unit and an oxypropylene unit, and the arrangement of the oxyethylene unit and the oxypropylene unit can be block-shaped or random. In addition, the molecular weight of such a polyoxyalkylene chain is preferably in the range of 100 to 3000, and more preferably in the range of 200 to 2500. Furthermore, when the polyoxyalkylene chain is a polyoxyethylenepolyoxypropylene chain, the ratio of the oxyethylene unit to the oxypropylene unit is preferably in the range of 100:0 to 50:50, more preferably in the range of 100:0 to 60:40, and even more preferably in the range of 100:0 to 70:30, in terms of mass ratio, from the viewpoint of the recoatability of the formed coating film, etc.

[0102] The polyester chain introduced into the side chain and / or the terminal of the compound having a polysiloxane structure can be, for example, a polyester chain containing polyols and polycarboxylic acids (including anhydrides and lower alkyl esters thereof) as constituent elements. As the polyol, diols and trivalent or higher polyols can be used, and as the polycarboxylic acid, dicarboxylic acids and trivalent or higher polycarboxylic acids can be used.

[0103] From the viewpoint of the scratch resistance of the formed coating film, the molecular weight of the compound (a2) having a second chemically reactive group, at least one chain selected from a polyoxyalkylene chain and a polyester chain, and a polysiloxane structure is preferably in the range of 200 to 4000 in the form of a number average molecular weight, more preferably in the range of 400 to 3000, and even more preferably in the range of 500 to 2500.

[0104] It should be noted that in this specification, the number average molecular weight and weight average molecular weight are values ​​calculated based on the chromatogram measured by gel permeation chromatography, with the molecular weight of standard polystyrene as the benchmark. The gel permeation chromatograph used "HLC8120GPC" (Tosoh Corporation). As chromatographic columns, four "TSKgel G-4000HXL", "TSKgel G-3000HXL", "TSKgel G-2500HXL", "TSKgel G-2000HXL" (all Tosoh (strain) company system, trade name) were used, and the mobile phase was tetrahydrofuran, the measurement temperature was 40°C, the flow rate was 1mL / min, and the detector was RI.

[0105] In the compound (a2) having a second chemically reactive group, at least one chain selected from a polyoxyalkylene chain and a polyester chain, and a polysiloxane structure, the ratio of the polysiloxane structure to the at least one chain selected from the polyoxyalkylene chain and the polyester chain is preferably in the range of 65:35 to 5:95, more preferably in the range of 55:45 to 10:90, and even more preferably in the range of 45:55 to 15:85, in terms of mass ratio, in the form of (polysiloxane structure): (at least one chain selected from the polyoxyalkylene chain and the polyester chain).

[0106] The ratio of the polysiloxane structure to at least one chain selected from the group consisting of a polyoxyalkylene chain and a polyester chain can be determined by proton NMR (Nuclear Magnetic Resonance). Specifically, in the proton NMR measurement (measurement device: Biospin Avance 600 (trade name) manufactured by Bruker, measurement solvent: chloroform-d, observation frequency: 150 MHz, cumulative number of times: 32 times), the ratio is calculated based on the integrated value of the peak (0.0 to 0.1 ppm, 0.4 to 0.6 ppm) of the proton of the alkyl group based on the polysiloxane structure and the integrated value of the peak (1.1 to 1.2 ppm, 3.5 to 3.7 ppm) of the proton of the oxyalkylene chain, thereby performing quantification.

[0107] If compounds suitable for use as the compound (a2) having a second chemically reactive group, at least one chain selected from a polyoxyalkylene chain and a polyester chain, and a polysiloxane structure are listed as examples, the following compounds are preferred: a dialkyl silicone having an epoxy group, a carboxyl group, a hydroxyl group, or an amino group as the second chemically reactive group on the side chain or at the terminal, and having a polyoxyalkylene chain having 2 to 4 carbon atoms as the polyoxyalkylene chain, and the following compounds are particularly preferred: a dimethyl silicone having an epoxy group or an amino group as the second chemically reactive group on the side chain or at the terminal, and having a polyoxyethylene-oxypropylene chain as the polyoxyalkylene chain. As the compound (a2) having a second chemically reactive group, at least one chain selected from a polyoxyalkylene chain and a polyester chain, and a polysiloxane structure, commercially available products may also be used. Examples of such commercial products include X-22-4741, KF-1002, and X-22-3939A (all manufactured by Shin-Etsu Silicone Co., Ltd.), DOWSIL BY16-760, DOWSIL BY16-876, DOWSIL FZ-3736 FLUID, DOWSIL SF8421 FLUID, and DOWSIL FZ-3789 (all manufactured by Dow-Tory Corporation).

[0108] The acrylic resin-modified silica particles of the present invention can be obtained by reacting silica particles (a1) bonded to an acrylic resin having a first chemically reactive group with a compound (a2) having a second chemically reactive group, at least one chain selected from a polyoxyalkylene chain and a polyester chain, and a polysiloxane structure.

[0109] The reaction between the silica particles (a1) and the compound (a2) can be carried out, for example, by mixing and heating the silica particles (a1) and the compound (a2) in an organic solvent.

[0110] Examples of the organic solvent include propylene glycol monomethyl ether, propylene glycol monoethyl ether, and propylene glycol monopropyl ether, and propylene glycol monomethyl ether is preferred.

[0111] The reaction conditions of the silica particles (a1) and the compound (a2) can be appropriately determined according to the combination of the first chemically reactive group / the second chemically reactive group, and can be generally heated and mixed at a temperature of 80 to 150° C. for 1 to 6 hours. In addition, from the viewpoint of the scratch resistance and transparency of the formed coating film, the ratio of the silica particles (a1) and the compound (a2) during the reaction is preferably set so that the mass ratio of the silica particles (a1) : the compound (a2) is within the range of 90:10 to 98:2, and more preferably set so that the mass ratio of the silica particles (a1) : the compound (a2) is within the range of 93:7 to 97:3.

[0112] The acrylic resin-modified silica particles of the present invention thus obtained comprise silica particles (A) and an acrylic resin (B) bonded to the silica particles (A), wherein the acrylic resin (B) is a modified silica particle having at least one chain selected from a polyoxyalkylene chain and a polyester chain and a polysiloxane structure.

[0113] In addition, as another specific method for forming a structure in which silica particles (A) are chemically bonded to an acrylic resin (B) having a polysiloxane structure and at least one chain selected from a polyoxyalkylene chain and a polyester chain, for example, there is a method of reacting silica particles (a11) having a polymerizable unsaturated group with a polymerizable unsaturated monomer mixture (a13), wherein the polymerizable unsaturated monomer mixture (a13) contains: a compound (a131) having a polymerizable unsaturated group and also having a polysiloxane structure; and a polymerizable unsaturated monomer (a132) having a polymerizable unsaturated group and also having at least one chain selected from a polyoxyalkylene chain and a polyester chain.

[0114] As a compound (a131) having a polymerizable unsaturated group and also having a polysiloxane structure, for example, a modified organic silicon compound modified by a polymerizable unsaturated group can be listed. As such a modified organic silicon compound, for example, the following modified organic silicon compound can be listed: a polymerizable unsaturated group is introduced into the side chain and / or the end of a compound having a polysiloxane structure such as dimethylpolysiloxane. The polymerizable unsaturated group introduced into the side chain and / or the end of the compound having a polysiloxane structure is a group that can be free radically polymerized with the polymerizable unsaturated group of the silica particles (a11) having the polymerizable unsaturated group, for example, vinyl, (meth) acryloyl, (meth) allyl, etc., but not limited to these.

[0115] As the compound (a131) having a polymerizable unsaturated group and also having a polysiloxane structure, a commercially available product may be used. Examples of such commercially available products include: “X-22-174ASX” (trade name, manufactured by Shin-Etsu Silicone Co., Ltd., single-end methacrylic acid-modified dimethyl silicone), “KF-2012” (trade name, manufactured by Shin-Etsu Silicone Co., Ltd., single-end methacrylic acid-modified dimethyl silicone), “X-22-174BX” (trade name, manufactured by Shin-Etsu Silicone Co., Ltd., single-end methacrylic acid-modified dimethyl silicone), “X-22-2426” (trade name, manufactured by Shin-Etsu Silicone Co., Ltd., single-end methacrylic acid-modified dimethyl silicone), “X-22-2404” (trade name, manufactured by Shin-Etsu Silicone Co., Ltd., single-end methacrylic acid-modified dimethyl silicone), “Silaplane FM-0711” (trade name, manufactured by JNC Corporation, single-end methacrylic acid-modified dimethyl silicone), “Silaplane FM-0721” (trade name, manufactured by JNC Corporation, single-end methacrylic acid-modified dimethyl silicone), “Silaplane "FM-0725" (trade name, manufactured by JNC, single-end methacrylic acid-modified dimethyl silicone), "BYK-UV 3500" (trade name, manufactured by BYK, polyether-modified polydimethylsiloxane with acrylic functional groups), "BYK-UV 3570" (trade name, manufactured by BYK, polyester-modified polydimethylsiloxane with acrylic functional groups), etc.

[0116] The polyoxyalkylene chain and polyester chain in the polymerizable unsaturated monomer (a132) having a polymerizable unsaturated group and at least one chain selected from a polyoxyalkylene chain and a polyester chain can be selected from the polyoxyalkylene chain and the polyester chain described in the item "compound (a2) having a second chemically reactive group, at least one chain selected from a polyoxyalkylene chain and a polyester chain, and a polysiloxane structure". In addition, the polymerizable unsaturated group is a group that can be free-radical polymerized with the polymerizable unsaturated group of the silica particles (a11) having the polymerizable unsaturated group, and examples thereof include: vinyl, (meth) acryloyl, (meth) allyl, etc., but are not limited to these.

[0117] As the polymerizable unsaturated monomer (a132) having a polymerizable unsaturated group and further having at least one chain selected from a polyoxyalkylene chain and a polyester chain, a commercially available product may be used. Examples of such commercially available products include: “Light Ester 130MA,” “Light Ester 041MA,” “Light Acrylate EC-A,” “Light Acrylate MTG-A,” “Light Acrylate 130A,” “Light Acrylate DPM-A,” “Light Acrylate P-200A,” and “Light Acrylate EHDG-AT” (all manufactured by Kyoeisha Chemical Co., Ltd.), “AM-30G,” “AM-90G,” “AM-130G,” “AM-230G,” “AM-30PG,” “M-20G,” “M-40G,” “M-90G,” “M-130G,” “M-230G,” “M-450G,” and “M-30PG” (all manufactured by Shin-Nakamura Chemical Co., Ltd.), “BLEMMER PME-100,” “BLEMMER PME-200,” “BLEMMER PME-400,” “BLEMMER PME-1000,” “BLEMMER PME-4000,” and “BLEMMER AME-400", "BLEMMER PE-90", "BLEMMER PE-200", "BLEMMER PE-350", "BLEMMER PP-1000", "BLEMMER PP-500", "BLEMMER PP-800", "BLEMMER 50PEP-300", "BLEMMER 55PET-800", "BLEMMER 10PPB-500B", "BLEMMER AE-200", "BLEMMER AE-400", "BLEMMER AP-200", "BLEMMER AP-400", "BLEMMER AP-550" (all made by NOF), "BYK-UV 3500", "BYK-UV 3570" (all made by BYK), etc.

[0118] The polymerizable unsaturated monomer mixture (a13) may contain polymerizable unsaturated monomers other than the compound (a131) and the polymerizable monomer (a132). Here, as polymerizable unsaturated monomers other than the compound (a131) and the polymerizable monomer (a132), for example, the polymerizable unsaturated monomers exemplified as “other polymerizable unsaturated monomers other than the polymerizable unsaturated monomer (a121) having the first chemically reactive group” described in the item of the already described “polymerizable unsaturated monomer mixture (a12)” can be used. In addition, in the present method, even the epoxy-containing polymerizable unsaturated monomers, carboxyl-containing polymerizable unsaturated monomers, hydroxyl-containing polymerizable unsaturated monomers, isocyanate-containing polymerizable unsaturated monomers, etc., which are exemplified in the description of the polymerizable unsaturated monomer (a121) having the first chemically reactive group, can be used as polymerizable unsaturated monomers other than the compound (a131) and the polymerizable monomer (a132). When the polymerizable unsaturated monomer mixture (a13) contains other polymerizable unsaturated monomers other than compound (a131) and polymerizable monomer (a132), the content of other polymerizable unsaturated monomers is preferably 99 mass % or less, and more preferably 97 mass % or less, based on the total mass of the polymerizable unsaturated monomer mixture (a13).

[0119] By reacting silica particles (a11) having a polymerizable unsaturated group with the above-mentioned polymerizable unsaturated monomer mixture (a13), acrylic resin-modified silica particles can be obtained, wherein the acrylic resin-modified silica particles include silica particles (A) and an acrylic resin (B) bonded to the silica particles (A), and the acrylic resin (B) has at least one chain selected from a polyoxyalkylene chain and a polyester chain and a polysiloxane structure.

[0120] The reaction of the silica particles (a11) with polymerizable unsaturated groups and the polymerizable unsaturated monomer mixture (a13) can be obtained by carrying out a polymerization reaction in the presence of a solvent. As the polymerization method, it is not particularly limited, and a known polymerization method can be used, wherein a solution polymerization method in which polymerization is carried out in an organic solvent and is appropriately carried out in the presence of a catalyst, a polymerization initiator, etc. can be preferably used. In addition, the organic solvent, the polymerization initiator, etc. used in the polymerization reaction are not particularly limited, for example, the organic solvent, the polymerization initiator, etc. exemplified by the polymerization reaction of the silica particles (a11) with polymerizable unsaturated groups and the polymerizable unsaturated monomer mixture (a12) can be used.

[0121] In the case where the acrylic resin (B) having at least one chain selected from a polyoxyalkylene chain and a polyester chain and a polysiloxane structure is an acrylic resin (B') also having a hydroxyl group, the acrylic resin (B') having a hydroxyl group can be obtained, for example, by containing a hydroxyl-containing polymerizable unsaturated monomer as a constituent component of the polymerizable unsaturated monomer mixture (a13). As the hydroxyl-containing polymerizable unsaturated monomer, the hydroxyl-containing polymerizable unsaturated monomers exemplified in the description of the polymerizable unsaturated monomer (a121) having a first chemically reactive group can be used. In addition, from the viewpoint of the scratch resistance and recoatability of the formed coating film, the hydroxyl value of the acrylic resin produced from the polymerizable unsaturated monomer mixture (a13) is preferably in the range of 60 to 140, more preferably in the range of 65 to 130, and particularly preferably in the range of 70 to 120.

[0122] As for the acrylic resin modified silica particles of the present invention, when the acrylic resin modified silica particles are formulated in a coating composition, a coating film having excellent scratch resistance and excellent adhesion (recoat adhesion) during repeated coating can be formed. The reason why the acrylic resin modified silica particles of the present invention exert such excellent effects may not be clear, but it can be inferred that: the acrylic resin modified silica particles of the present invention have a polysiloxane structure and are segregated on the coating film surface, so they have excellent scratch resistance, and the acrylic resin modified silica particles of the present invention have at least one chain selected from a polyoxyalkylene chain and a polyester chain, so that the wettability during repeated coating becomes good, so that a coating film having excellent recoat adhesion is formed.

[0123] Moreover, the acrylic resin modified silica particles of the present invention can form a coating film with excellent transparency when the acrylic resin modified silica particles are mixed in a coating composition. The reason why the acrylic resin modified silica particles of the present invention exert such an excellent effect is not necessarily clear, but it can be inferred that: the acrylic resin modified silica particles contain acrylic resin, so the acrylic resin modified silica particles and the binder component contained in the coating composition have a high affinity, so a coating film with excellent transparency is formed.

[0124] Coating composition

[0125] The present invention also provides a coating composition comprising the acrylic resin-modified silica particles of the present invention and a binder component.

[0126] From the viewpoints of the scratch resistance, recoatability and transparency of the formed coating film, the amount of the acrylic resin-modified silica particles added when providing the present coating composition is preferably 0.3 to 90 parts by mass, more preferably 0.5 to 30 parts by mass, and even more preferably 1 to 15 parts by mass, based on 100 parts by mass of the total solid content of the binder component.

[0127] As the binder component used in the coating composition of the present invention, various binder components known for coatings can be used, but preferably a binder component containing a base resin having a crosslinkable functional group and a curing agent is used.

[0128] Examples of the crosslinkable functional group of the base resin include carboxyl, hydroxyl, epoxy, and silanol groups. Examples of the type of base resin include acrylic resins, polyester resins, alkyd resins, polyurethane resins, epoxy resins, and fluororesins. Examples of curing agents include polyisocyanate compounds, blocked polyisocyanate compounds, melamine resins, urea-formaldehyde resins, carboxyl-containing compounds, carboxyl-containing resins, epoxy-containing resins, and epoxy-containing compounds.

[0129] Preferred combinations of the base resin / curing agent include hydroxyl-containing resin / polyisocyanate compound, carboxyl-containing resin / epoxy-containing resin, hydroxyl-containing resin / blocked polyisocyanate compound, hydroxyl-containing resin / melamine resin, and the like.

[0130] As the base resin, a hydroxyl-containing resin is preferred. As the hydroxyl-containing resin, there is no particular limitation as long as it contains a hydroxyl group, and a known resin as a thermosetting resin can be preferably used. For example, alkyd resins, polyester resins, acrylic resins, cellulose resins, etc. can be listed. From the viewpoints of weather resistance, scratch resistance, and transparency of the formed coating film, a hydroxyl-containing acrylic resin is preferably included.

[0131] The hydroxyl-containing acrylic resin can be produced by copolymerizing a hydroxyl-containing polymerizable unsaturated monomer and another polymerizable unsaturated monomer copolymerizable with the hydroxyl-containing polymerizable unsaturated monomer. The hydroxyl-containing polymerizable unsaturated monomer is a compound having one or more hydroxyl groups and one or more polymerizable unsaturated groups in one molecule.

[0132] As the hydroxyl-containing polymerizable unsaturated monomer, specifically, a monoester of acrylic acid or methacrylic acid and a diol having 2 to 10 carbon atoms is preferred, and examples thereof include: 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, caprolactone-modified hydroxyl-containing (meth)acrylate, 4-hydroxymethylcyclohexyl (meth)acrylate, etc. Examples of commercially available caprolactone-modified hydroxyl-containing (meth)acrylates include "PLACCEL FM" (trade name, manufactured by Daicel Chemical Co., Ltd.), and examples of commercially available 4-hydroxymethylcyclohexyl (meth)acrylate include "CHDMMA" (trade name, manufactured by Nippon Chemical Co., Ltd.).

[0133] As the hydroxyl-containing polymerizable unsaturated monomer, from the viewpoint of the scratch resistance of the formed coating film, it is particularly preferred to use a polymerizable unsaturated monomer having a hydroxyl-containing hydrocarbon group having 2 to 20 carbon atoms, and specifically, it is preferred to use: 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 4-hydroxymethylcyclohexyl acrylate, etc. The hydroxyl group of the hydroxyl-containing polymerizable unsaturated monomer functions as a crosslinking functional group of the obtained copolymer resin.

[0134] The other copolymerizable polymerizable unsaturated monomer is a compound other than the above-mentioned hydroxyl-containing polymerizable unsaturated monomer and having one or more polymerizable unsaturated groups in one molecule. Specific examples thereof are listed in the following (1) to (11).

[0135] (1) Aromatic polymerizable unsaturated monomers: for example, styrene, α-methylstyrene, vinyltoluene, etc.

[0136] (2) Polymerizable unsaturated monomers containing an alicyclic hydrocarbon group having 3 to 20 carbon atoms: for example, polymerizable unsaturated monomers containing a bridged alicyclic hydrocarbon group having 10 to 20 carbon atoms, such as isobornyl (meth)acrylate, tricyclodecanyl (meth)acrylate, adamantyl (meth)acrylate, 3,5-dimethyladamantyl (meth)acrylate, and 3-tetracyclododecyl (meth)acrylate; polymerizable unsaturated monomers containing an alicyclic hydrocarbon group having 3 to 12 carbon atoms, such as cyclohexyl (meth)acrylate, 4-methylcyclohexylmethyl (meth)acrylate, 4-ethylcyclohexylmethyl (meth)acrylate, 4-methoxycyclohexylmethyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, cyclooctyl (meth)acrylate, cyclododecyl (meth)acrylate, and tetrahydrofurfuryl (meth)acrylate.

[0137] (3) A polymerizable unsaturated monomer having a hydrocarbon group having 8 or more carbon atoms and a branched structure: Examples thereof include 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isotetradecyl (meth)acrylate, isostearyl (meth)acrylate, etc. Commercially available products include "isooctadecyl acrylate" (trade name, manufactured by Osaka Organic Chemical Industry Co., Ltd.).

[0138] (4) Linear or branched alkyl esters of (meth)acrylic acid having 1 to 7 carbon atoms: methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, etc.

[0139] (5) Linear alkyl esters of (meth)acrylic acid having 8 to 22 carbon atoms: for example, dodecyl (meth)acrylate, octadecyl (meth)acrylate, and the like.

[0140] (6) Epoxy-containing polymerizable unsaturated monomers: for example, glycidyl (meth)acrylate, etc.

[0141] (7) Nitrogen-containing polymerizable unsaturated monomers: for example, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, vinylpyridine, vinylimidazole, etc.

[0142] (8) Other vinyl compounds: for example, vinyl acetate, vinyl propionate, vinyl chloride, vinylidene chloride, divinyl ether, and versatate vinyl carbonates such as "VeoVa 9" and "VeoVa 10" (trade names, manufactured by Japan Epoxy Resin Co., Ltd.).

[0143] (9) Nitrile compounds containing an unsaturated group: for example, (meth)acrylonitrile, etc.

[0144] (10) Polymerizable unsaturated monomers containing acidic functional groups: for example, unsaturated monomers containing carboxyl groups such as (meth)acrylic acid, crotonic acid, itaconic acid, maleic acid and maleic anhydride; unsaturated monomers containing sulfonic acid groups such as vinyl sulfonic acid and (meth)acrylic acid sulfoethyl ester; and acidic phosphate-based unsaturated monomers such as 2-(meth)acryloyloxyethyl phosphate, 2-(meth)acryloyloxypropyl phosphate, 2-(meth)acryloyloxy-3-chloropropyl phosphate and 2-(meth)acryloyloxyethylphenyl phosphate.

[0145] (11) Alkoxysilyl group-containing polymerizable unsaturated monomers: Examples thereof include vinyl trimethoxysilane, vinyl triethoxysilane, acryloxyethyl trimethoxysilane, methacryloxyethyl trimethoxysilane, acryloxypropyl trimethoxysilane, methacryloxypropyl trimethoxysilane, acryloxypropyl triethoxysilane, methacryloxypropyl triethoxysilane, and vinyl tri(β-methoxyethoxy)silane.

[0146] The above other copolymerizable polymerizable unsaturated monomers may be used alone or in combination of two or more.

[0147] The hydroxyl-containing polymerizable unsaturated monomer is copolymerized with the polymerizable unsaturated monomer mixture composed of the above other polymerizable unsaturated monomers to obtain a hydroxyl-containing acrylic resin. In view of the scratch resistance, recoatability, transparency and finished product performance of the formed coating film, the hydroxyl-containing polymerizable unsaturated monomer is preferably used in an amount of 15 to 50% by mass, preferably 20 to 45% by mass, based on the total mass of the copolymerizable monomer components.

[0148] As other polymerizable unsaturated monomers, it is desirable to use the above-mentioned monomer (1) from the aspects of finished product performance (especially gloss), water resistance and weather resistance, and the preferred usage ratio is about 3 to 40% by mass, preferably about 5 to 30% by mass, based on the total mass of the copolymerizable monomer components.

[0149] In addition, as other polymerizable unsaturated monomers, it is ideal to use the above-mentioned monomer (2) from the aspects of finished product performance, scratch resistance and water resistance, and its usage ratio is preferably about 3 to 40 mass %, preferably about 5 to 30 mass %, based on the total mass of the copolymerizable monomer components.

[0150] In addition, as other polymerizable unsaturated monomers, from the perspective of wettability to the coated object and finished product performance, it is ideal to use the above-mentioned monomer (3), and its usage ratio is preferably about 3 to 45 mass %, preferably about 8 to 40 mass %, based on the total mass of the copolymerizable monomer components.

[0151] Furthermore, based on the total mass of the above-mentioned comonomer components, from the viewpoint of obtaining a resin having extremely excellent acid resistance and scratch resistance of the coating film, the total mass of monomer (1), monomer (2) and monomer (3) is preferably within the range of about 35 to 85 mass %, preferably about 40 to 80 mass %, based on the total mass of the comonomer components.

[0152] Among other polymerizable unsaturated monomers, polymerizable unsaturated monomers containing acidic functional groups such as carboxyl-containing unsaturated monomers, sulfonic acid-containing unsaturated monomers, and acidic phosphate-based unsaturated monomers can act as internal catalysts when the resulting hydroxyl-containing resin undergoes a cross-linking reaction with a polyisocyanate compound, and their usage amount is preferably in the range of about 0.1 to 5% by mass based on the total amount of the monomer mixture constituting the resin, and can be used in the range of about 0.5 to 3% by mass.

[0153] The copolymerization method for copolymerizing the monomer mixture to obtain the hydroxyl-containing acrylic resin is not particularly limited, and a known copolymerization method can be used. In particular, a solution polymerization method in which polymerization is performed in an organic solvent in the presence of a polymerization initiator is preferably used.

[0154] As the organic solvent used in the above-mentioned solution polymerization method, for example, aromatic solvents such as toluene, xylene, and high-boiling aromatic hydrocarbons; ester solvents such as ethyl acetate, butyl acetate, 3-methoxybutyl acetate, ethylene glycol ethyl ether acetate, and propylene glycol methyl ether acetate; ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone, and methyl amyl ketone; glycol ether solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, ethylene glycol monobutyl ether, and propylene glycol monomethyl ether; propyl propionate, butyl propionate, ethoxyethyl propionate, etc. As commercial products of high-boiling aromatic hydrocarbons, for example, "Swasol 1000" (trade name, manufactured by COSMO Oil Co., Ltd., a high-boiling petroleum solvent) can be listed.

[0155] These organic solvents may be used alone or in combination of two or more. In particular, when the hydroxyl-containing acrylic resin has a high hydroxyl value, it is preferred to use a high-boiling point ester solvent or ketone solvent from the perspective of the solubility of the resin as the organic solvent. In addition, a high-boiling point aromatic solvent may be further used in combination.

[0156] Examples of the polymerization initiator that can be used in the copolymerization of the hydroxyl-containing acrylic resin include known radical polymerization initiators such as 2,2′-azobisisobutyronitrile, benzoyl peroxide, 2,2-di(tert-amylperoxy)butane, di-tert-butyl peroxide, di-tert-amyl peroxide, tert-butyl peroctoate, and 2,2′-azobis(2-methylbutyronitrile).

[0157] The hydroxyl-containing acrylic resin may be composed of one copolymer or two or more copolymers. From the viewpoints of abrasion resistance and recoatability, the hydroxyl value of the hydroxyl-containing acrylic resin is preferably in the range of 10 to 200 mgKOH / g, more preferably 50 to 200 mgKOH / g, and even more preferably 80 to 200 mgKOH / g.

[0158] The weight average molecular weight of the hydroxyl-containing acrylic resin is preferably within a range of 3,000 to 40,000, more preferably 4,000 to 30,000, and particularly preferably 5,000 to 20,000, from the viewpoint of the scratch resistance and transparency of the formed coating film.

[0159] The glass transition temperature of the hydroxyl-containing acrylic resin is preferably in the range of -30°C to 50°C, particularly preferably -20°C to 40°C, from the viewpoint of the scratch resistance and transparency of the formed coating film.

[0160] As a curing agent, polyisocyanate compounds (including blocked polyisocyanate compounds), melamine resins, cyanuric acid diamine resins, amino resins such as urea-formaldehyde resins can be used. From the perspective of obtaining a coating film with better weather resistance, scratch resistance, coating film hardness, adhesion, etc., polyisocyanate compounds and / or melamine resins are preferred.

[0161] Polyisocyanate compounds are compounds having two or more isocyanate groups in one molecule. As polyisocyanate compounds, for example, aliphatic diisocyanates such as hexamethylene diisocyanate or trimethyl hexamethylene diisocyanate; cyclic aliphatic diisocyanates such as hydrogenated xylylene diisocyanate or isophorone diisocyanate; organic diisocyanates such as aromatic diisocyanates such as toluene diisocyanate or 4,4'-diphenylmethane diisocyanate, or adducts of these organic diisocyanates with polyols, low molecular weight polyester resins or water, or cyclized polymers of the organic diisocyanates as described above, and isocyanate / biuret bodies, etc., can also be used compounds formed by blocking these polyisocyanate compounds using blocking agents. In the case of using blocked isocyanate compounds, it is preferred to use a dissociation catalyst in combination.

[0162] Representative commercially available examples of the isocyanate compounds include BURNOCK D-750, BURNOCK D-800, BURNOCK DN-950, BURNOCK DN-970 or 15-455 (these are trade names, manufactured by DIC Corporation), Sumidur N3300, Sumidur N3390, Desmodur N3400, Desmodur N3900 (these are trade names, manufactured by Sumitomo-Bayer Urethane Co., Ltd.), DURANATE 24A-100, DURANATE TPA-100, DURANATE TLA-100, DURANATE P301-75E (these are trade names, manufactured by Asahikasei Chemicals Co., Ltd.), and the like.

[0163] As the blocked polyisocyanate compound having an isocyanate group, there can be cited polyisocyanate compounds obtained by blocking the above-mentioned polyisocyanate compound having a free isocyanate group with a known blocking agent such as oxime, phenol, alcohol, lactam, malonate, thiol, etc. As examples of their representative commercial products, there can be cited BURNOCK D-550 (trade name, manufactured by DIC Corporation) or DURANATE SBN-70 (trade name, manufactured by Asahi Kasei Corporation), etc.

[0164] As the melamine resin, for example, a melamine resin obtained by etherifying the methylol groups of methylolated melamine with a monohydric alcohol having 1 to 8 carbon atoms can be preferably used. The etherified melamine resin may be a resin in which all the methylol groups of the methylolated melamine are etherified, or a resin in which a part of the methylol groups are etherified and a methylol group or an imino group remains.

[0165] Specific examples of the etherified melamine resin include alkyl etherified melamines such as methyl etherified melamine, ethyl etherified melamine, and butyl etherified melamine. The etherified melamine resin may be used alone or in combination of two or more.

[0166] As commercially available products of the above-mentioned melamine resin, for example, butylated melamine resin (Mitsui Chemicals, Inc.; U-VAN 20SE-60, U-VAN 225, DIC Corporation; Super Beckamine G840, Super Beckamine G821, etc.); methylated melamine resin (Nihon Cytec Industries, Ltd.; Cymel 303, Sumitomo Chemical Co., Ltd.; Sumimar M-100, Sumimar M-40S, etc.); methylated melamine resin (Nihon Cytec Industries, Ltd.; Cymel 303, Cymel 325, Cymel 327, Cymel 350, Cymel 370, Sumitomo Chemical Co., Ltd. Sumimar M55, etc.); methylated and butylated mixed etherified melamine resin (Nihon Cytec Industries, Ltd.; Cymel 303, Cymel 325, Cymel 327, Cymel 350, Cymel 370, Sumitomo Chemical Co., Ltd. Sumimar M55, etc.); Industries Co., Ltd.; Cymel253, Cymel202, Cymel238, Cymel254, Cymel272, Cymel1130, Sumitomo Chemical Co., Ltd.: Sumimar M66B, etc.); methylated, isobutylated mixed etherified melamine resins (Nihon Cytec Industries Cymel XV805, etc.) and other melamine resins.

[0167] The curing agent may be appropriately added so that the coating film is cured and has sufficient performance. From the viewpoint of the curability of the resulting coating film, the hydroxyl-containing resin / curing agent ratio is preferably in the range of 80 / 20 to 50 / 50 in terms of mass ratio.

[0168] When a polyisocyanate compound is used as a curing agent, the mixing ratio thereof is preferably such that the equivalent ratio (NCO / OH) of the isocyanate group of the polyisocyanate compound to the hydroxyl group of the hydroxyl-containing resin in the coating composition of the present invention is usually 0.5 to 2.0, particularly 0.7 to 1.5.

[0169] In the present coating composition manufacturing method, the coating composition may further contain the following substances, either alone or in combination of two or more thereof: a curing catalyst, a pigment, an ultraviolet absorber (for example, a benzotriazole absorber, a triazine absorber, a salicylic acid derivative absorber, a benzophenone absorber, etc.), a light stabilizer (for example, a hindered piperidine, etc.), a thickener, a defoamer, a plasticizer, an organic solvent, a surface conditioner, an anti-settling agent, and other common coating additives.

[0170] Examples of the curing catalyst include organic metal catalysts such as tin octanoate, dibutyltin di(2-ethylhexanoate), dioctyltin di(2-ethylhexanoate), dioctyltin diacetate, dibutyltin dilaurate, dibutyltin oxide, dioctyltin oxide, and lead 2-ethylhexanoate; acid compounds such as p-toluenesulfonic acid, dodecylbenzenesulfonic acid, dinonylnaphthalenesulfonic acid, dinonylnaphthalene disulfonic acid, monobutylphosphoric acid, dibutylphosphoric acid, octylphosphoric acid, and di(2-ethylhexyl)phosphoric acid; and base compounds such as trimethylamine, triethylamine, dimethylcyclohexylamine, N-tetramethylhexane-1,6-diamine, N-pentamethyldiethylenetriamine, and 2-methyl-1,4-diazabicyclo〔2,2,2〕octane. These catalysts may be used alone or in combination of two or more.

[0171] When the coating composition contains a curing catalyst, the amount of the curing catalyst is preferably in the range of 0.05 to 10 parts by mass, more preferably in the range of 0.1 to 5 parts by mass, and even more preferably in the range of 0.2 to 3 parts by mass, based on 100 parts by mass of the total resin solid content of the hydroxyl-containing resin and the curing agent.

[0172] When the coating composition contains an ultraviolet absorber, the amount of the ultraviolet absorber is preferably in the range of 0.1 to 10 parts by mass, more preferably in the range of 0.2 to 5 parts by mass, and further preferably in the range of 0.3 to 4 parts by mass, based on 100 parts by mass of the total resin solid content of the hydroxyl-containing resin and the curing agent.

[0173] When the coating composition contains a light stabilizer, the amount of the light stabilizer is preferably in the range of 0.1 to 10 parts by mass, more preferably in the range of 0.2 to 5 parts by mass, and even more preferably in the range of 0.3 to 4 parts by mass, based on 100 parts by mass of the total resin solid content of the hydroxyl-containing resin and the curing agent.

[0174] The coating composition may be a one-component coating or a multi-component coating such as a two-component coating. In the coating composition of the present invention, when an unblocked polyisocyanate compound is used as a curing agent, from the viewpoint of storage stability, it is preferred to use a two-component coating containing a main component including a hydroxyl-containing resin and a curing agent, and to mix the two immediately before use.

[0175] The form of the coating composition is not particularly limited, but is preferably an organic solvent solution type or a non-aqueous dispersion type.

[0176] Examples of the organic solvent include ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; esters such as ethyl acetate, butyl acetate, methyl benzoate, ethyl ethoxypropionate, ethyl propionate, and methyl propionate; ethers such as tetrahydrofuran, dioxane, and dimethoxyethane; glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, and 3-methoxybutyl acetate; aromatic hydrocarbons; aliphatic hydrocarbons, and the like.

[0177] These can be used in combination as appropriate depending on the purpose of adjusting the viscosity, adjusting the coating properties, and the like.

[0178] The solid content of the coating composition is not particularly limited. For example, from the perspective of smoothness of the cured coating film and shortening of the drying time, it is preferably appropriately adjusted in advance using a solvent such as the above-mentioned organic solvent so that the viscosity obtained by Ford Cup No. 4 at 20° C. is in the range of 15 to 60 seconds.

[0179] In this specification, solid content refers to the residue after removing volatile components, and the residue can be solid or liquid at room temperature. The mass of the solid content can be calculated as follows: the ratio of the mass of the residue after drying to the mass before drying is set as the solid content rate, and the solid content rate is multiplied by the mass of the sample before drying.

[0180] Coating method

[0181] The coating composition is not particularly limited to the coating object. For example, cold-rolled steel sheets, galvanized steel sheets, zinc alloy steel sheets, stainless steel sheets, tin-plated steel sheets and other steel sheets, aluminum sheets, aluminum alloy sheets and other metal substrates, various plastic raw materials, etc. In addition, the coating composition can also be used for the bodies of various vehicles such as automobiles, bicycles, and containers.

[0182] In addition, the coated object may be an object having a surface treatment such as phosphate treatment, chromate treatment, or composite oxide treatment applied to the metal surface of the above-mentioned metal substrate or vehicle body. Furthermore, the coated object may be an object having a base coating film such as various electrodeposition coatings formed on the above-mentioned metal substrate or vehicle body, an object having the base coating film and a mid-coat coating film formed thereon, an object having a base coating film, a mid-coat coating film, and a primer coating film formed thereon, or an object having a base coating film, a mid-coat coating film, a primer coating film, and a clear coating film formed thereon.

[0183] The coating method of the coating composition is not particularly limited, and for example, coating methods such as air spray coating, airless spray coating, rotary atomization coating, and curtain coating can be listed, and wet coating can be formed by these methods. In these coating methods, electrostatic application can also be performed as required. Among them, air spray coating or rotary atomization coating is particularly preferred.

[0184] The coating amount of the coating composition is usually preferably set to an amount of about 10 to 60 μm in terms of cured film thickness.

[0185] In addition, when air spray coating, airless spray coating and rotary atomization coating are performed, the viscosity of the present coating is preferably appropriately adjusted using a solvent such as an organic solvent so that it becomes a viscosity range suitable for the coating, usually a viscosity range of about 15 to 60 seconds at 20°C in a Ford Cup No. 4 viscometer.

[0186] The curing of the wet coating film formed by applying the coating composition to the coated object can be carried out by heating, and the heating can be carried out by a known heating unit, for example, a drying furnace such as a hot air furnace, an electric furnace, and an infrared induction heating furnace. The heating temperature is 60 to 180° C., preferably in the range of 70 to 150° C. Preferably, the heating time is not particularly limited, but is in the range of 10 to 60 minutes, preferably 15 to 30 minutes.

[0187] The coating composition can be preferably used as a top clear coating composition from the viewpoint of obtaining a cured coating film having excellent scratch resistance and coating film appearance. The coating composition can be particularly suitably used as a coating for automobiles.

[0188] Multilayer coating film forming method

[0189] As a method for forming a multilayer coating film in which the coating composition of the present invention is applied as a top layer clear coating paint, the following multilayer coating film forming method can be listed, which is a method for forming a multilayer coating film by sequentially applying at least one layer of colored base coating paint and at least one layer of clear coating paint to a coated object, and the multilayer coating film forming method includes: applying the coating composition of the present invention as the topmost clear coating paint.

[0190] Specifically, for example, there can be mentioned: a two-coat-one-bake method for forming a multilayer coating film, in which an undercoat is formed by electrodeposition coating, the undercoat is cured, a middle-coat is formed on the undercoat by a middle-coat coating, the middle-coat is cured, a colored basecoat is applied on the middle-coat, and in order to promote the volatilization of the solvent in the colored basecoat as needed without curing the coating film, for example, preheating is performed at 40 to 90° C. for about 3 to 30 minutes, and the coating composition of the present invention is applied as a clearcoat on the uncured colored basecoat, and the colored basecoat and the clearcoat are cured together; a three-coat-one-bake method for forming a multilayer coating film, in which an undercoat is formed by electrodeposition coating, the undercoat is cured, and the middle-coat is cured. A lower coating film is formed, and after the lower coating film is cured, a middle coating film is formed on the lower coating film by a middle coating material. Without curing the middle coating film, in order to promote the volatilization of the solvent in the middle coating paint as needed, preheating is performed at 40 to 90° C. for about 3 to 30 minutes, for example, and a colored base coating paint is applied on the uncured middle coating film. Without curing the coating film, in order to promote the volatilization of the solvent in the colored base coating paint as needed, preheating is performed at 40 to 90° C. for about 3 to 30 minutes, for example, and after applying the coating composition of the present invention as a clear coating paint on the uncured colored base coating film, the middle coating film, the colored base coating film and the clear coating film are cured together.

[0191] As the intermediate coating used in the above, conventionally known conventional thermosetting intermediate coatings can be used, specifically, for example, a coating formed by appropriately combining crosslinking agents such as amino resins, polyisocyanate compounds, blocked polyisocyanate compounds, and reactive functional groups contained in a matrix resin such as acrylic resins, polyester resins, alkyd resins, and polyurethane resins. The reactive functional groups contained in the above-mentioned matrix resins are preferably hydroxyl groups.

[0192] As the intermediate coating material, for example, water-based coating material, organic solvent-based coating material, and powder coating material can be used. Among them, water-based coating material is preferred from the viewpoints of reducing environmental load and the finished appearance of the coating film.

[0193] In addition, as the primer coating used in the above, conventionally known conventional thermosetting primer coatings can be used, specifically, for example, a coating obtained by appropriately combining a crosslinking agent such as an amino resin, a polyisocyanate compound, a blocked polyisocyanate compound, and a reactive functional group contained in a matrix resin such as an acrylic resin, a polyester resin, an alkyd resin, or a polyurethane resin can be used. The reactive functional group contained in the above matrix resin is preferably a hydroxyl group.

[0194] As the primer coating material, for example, water-based coating materials, organic solvent-based coating materials, and powder coating materials can be used. Among them, water-based coating materials are preferred from the viewpoints of reducing environmental load and improving the finished appearance of the coating film.

[0195] In the above-mentioned multilayer coating film forming method, when two or more clear coating layers are applied, as the clear coating paint other than the uppermost layer, the coating composition of the present invention may be used, or a conventionally known thermosetting clear coating paint may be used.

[0196] Example

[0197] Hereinafter, manufacturing examples, embodiments and comparative examples are listed to further specifically describe the present invention. However, the present invention is not limited to these examples. In each example, "parts" and "%" are based on mass unless otherwise specified. In addition, the film thickness of the coating film is based on the film thickness of the cured coating film.

[0198] Production of silica particles (a11) having polymerizable unsaturated groups

[0199] After adding 333 parts (100 parts solid content) of "PGM-ST" (trade name, manufactured by Nissan Chemical Industries, Ltd., average primary particle size of silica: 15 nm, silica concentration: 30% by mass, dispersion medium: propylene glycol monomethyl ether) and 10 parts of deionized water to a separable flask equipped with a reflux condenser, a thermometer and a stirrer, 10 parts of "KBM-503" (trade name, manufactured by Shin-Etsu Chemical Industries, Ltd., γ-methacryloxypropyltrimethoxysilane) were added, and a dehydration condensation reaction was carried out while stirring at 80°C for 2 hours. Then, 0.03 parts of tetra-n-butylammonium fluoride was added, and the mixture was further stirred for 1 hour to react. After the reaction was completed, 30 parts of propylene glycol monomethyl ether was added, and the volatile components were then distilled off under reduced pressure to obtain a dispersion of silica particles (a11) containing polymerizable unsaturated groups with a solid content of 40% of surface-modified silica particles. Preparation of dispersion of acrylic resin-modified silica particles (AB)

[0200] Example 1

[0201] Into a separable flask equipped with a reflux condenser, a thermometer, a stirrer, and a nitrogen inlet, 135 parts of propylene glycol monomethyl ether was placed, and the temperature was raised to 100°C under nitrogen flow. After reaching 100°C, a monomer mixture consisting of 312.5 parts (125 parts of solid content) of the above-mentioned polymerizable unsaturated group-containing silica particles (a11), 19 parts of 2-hydroxyethyl methacrylate (HEMA), 30 parts of styrene (St), 1 part of methyl methacrylate (MMA), 49 parts of 2-ethylhexyl acrylate (2EHA), 1 part of acrylic acid (AAc), and 1.5 parts of 2,2'-azobis(2-methylbutyronitrile) (polymerization initiator) was added dropwise over 2 hours. Then, after aging at 100°C for 1 hour, a mixed solution of 0.5 parts of 2,2'-azobis(2-methylbutyronitrile) (polymerization initiator) and 20 parts of propylene glycol monomethyl ether was added, and further aged for 2 hours. Next, 10 parts of "X-22-4741" (trade name, manufactured by Shin-Etsu Silicone Co., Ltd., side chain type epoxy / polyoxyethylene-oxypropylene chain modified dimethyl silicone, the mass ratio of the polysiloxane structure to the polyoxyalkylene chain calculated by the following method is 22 / 78) was added and further aged for 3 hours. The polymerization rate calculated from the non-volatile components was 99%. Thereafter, propylene glycol monomethyl ether was added, and the solvent was replaced by azeotropic distillation under reduced pressure to obtain an acrylic resin modified silica particle (AB-1) dispersion having a non-volatile component of 40% as measured.

[0202] Examples 2 to 13, Comparative Example 1

[0203] Acrylic resin-coated silica particles (AB-2) to (AB-14) were obtained in the same manner as in Example 1 except that the formulations shown in Tables 1 and 2 were used.

[0204]

[0205]

[0206] It should be noted that (Note 1) to (Note 3) in the table have the following meanings.

[0207] (Note 1) “X-22-174ASX”: Trade name of a single-end methacrylic acid-modified dimethyl silicone manufactured by Shin-Etsu Silicone Co., Ltd.

[0208] (Note 2) "Light Ester 130MA": trade name, manufactured by Kyoeisha Chemical Co., Ltd., methoxy polyethylene glycol methacrylate.

[0209] (Note 3) “KF-1002”: trade name, manufactured by Shin-Etsu Silicone Co., Ltd., side chain type epoxy / polyoxyethylene-oxypropylene chain-modified dimethyl silicone, the mass ratio of the polysiloxane structure to the polyoxyalkylene chain calculated by the following method is 50 / 50.

[0210] The mass ratio of the polysiloxane structure to the polyoxyalkylene chain is calculated based on analysis by proton NMR.

[0211] Specifically, in the above analysis using proton NMR, Biospin Avance 600 (trade name) manufactured by Bruker was used as a proton NMR measuring device, chloroform-d was used as a solvent, and under the measurement conditions of an observation frequency of 150 MHz and a cumulative number of 32 times, the integrated value of the peak (0.0 to 0.1 ppm, 0.4 to 0.6 ppm) of the protons of the alkyl group based on the polysiloxane structure and the integrated value of the peak (1.1 to 1.2 ppm, 3.5 to 3.7 ppm) of the protons of the oxyalkylene chain were calculated. From the ratio of the obtained integrated value of the peak (0.0 to 0.1 ppm, 0.4 to 0.6 ppm) of the protons of the alkyl group based on the polysiloxane structure to the integrated value of the peak (1.1 to 1.2 ppm, 3.5 to 3.7 ppm) of the protons of the oxyalkylene chain, the mass ratio of the polysiloxane structure to the above polyoxyalkylene chain was calculated.

[0212] Embodiment 14

[0213] 135 parts of propylene glycol monomethyl ether were placed in a separable flask equipped with a reflux condenser, a thermometer, a stirrer, and a nitrogen inlet, and the temperature was raised to 100° C. under nitrogen flow. After reaching 100° C., a monomer mixture consisting of 312.5 parts (solid content 125 parts) of the above-mentioned polymerizable unsaturated group-containing silica particles (a11) dispersion, 19 parts of 2-hydroxyethyl methacrylate (HEMA), 27.4 parts of styrene (St), 1 part of methyl methacrylate (MMA), 44.7 parts of 2-ethylhexyl acrylate (2EHA), 1 part of acrylic acid (AAc), 2.4 parts of "X-22-174ASX" (trade name, manufactured by Shin-Etsu Silicone Co., Ltd., single-end methacrylic acid-modified dimethyl silicone), 4.6 parts of "Light Ester 130MA" (trade name, manufactured by Kyoeisha Chemical Co., Ltd., methoxy polyethylene glycol methacrylate) and 1.5 parts of 2,2'-azobis(2-methylbutyronitrile) (polymerization initiator) was added dropwise over 2 hours. Next, after aging at 100°C for 1 hour, a mixed solution of 0.5 parts of 2,2'-azobis(2-methylbutyronitrile) (polymerization initiator) and 20 parts of propylene glycol monomethyl ether was added and further aged for 2 hours. The polymerization rate calculated from the non-volatile components was 99%. Thereafter, propylene glycol monomethyl ether was added and azeotropic distillation was performed under reduced pressure to replace the solvent, thereby obtaining an acrylic resin modified silica particle (AB-15) dispersion having a non-volatile component of 40% as measured.

[0214] Examples 15 to 17, Comparative Example 2

[0215] Except having used the formulation shown in Table 3, it carried out similarly to Example 14, and obtained the acrylic resin-coated silica particles (AB-16) - (AB-19).

[0216] [Table 3]

[0217]

[0218] It should be noted that (Note 4) in the table has the following meanings.

[0219] (Note 4) “KF-2012”: Trade name of a single-end methacrylic acid-modified dimethyl silicone manufactured by Shin-Etsu Silicone Co., Ltd.

[0220] Production of hydroxyl-containing acrylic resin

[0221] Production Example 1

[0222] 30 parts of "Swazol 1000" (trade name, manufactured by COSMO FUJIU CO., LTD., aromatic organic solvent) and 10 parts of n-butanol were placed in a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube, and a dropping device. While blowing nitrogen into the reaction vessel, the charged liquid was stirred at 125°C, and a monomer mixture consisting of 35 parts of 2-hydroxypropyl acrylate, 20 parts of styrene, 45 parts of isobutyl methacrylate, and 1.5 parts of 2,2'-azobis(2-methylbutyronitrile) (polymerization initiator) was dropped therein at a uniform rate over 4 hours. After aging at 125°C for 30 minutes, a solution consisting of 0.5 parts of 2,2'-azobis(2-methylbutyronitrile) and 5.0 parts of "Swasol 1000" was dropped therein at a uniform rate over 1 hour. After aging at 125°C for 1 hour, the mixture was cooled and diluted by adding 6 parts of isobutyl acetate to obtain a hydroxyl-containing acrylic resin solution having a solid content concentration of 65% by mass. The obtained hydroxyl-containing acrylic resin had a hydroxyl value of 151 mgKOH / g, a weight average molecular weight of 7000, and a glass transition temperature of 36.4°C.

[0223] Production of acrylic resin having hydroxyl group and alkoxysilane group

[0224] Production Example 2

[0225] 30 parts of "Swazol 1000" (trade name, manufactured by COSMO FUJIU CO., LTD., aromatic organic solvent) and 10 parts of n-butanol were placed in a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube, and a dropping device. While blowing nitrogen into the reaction vessel, the charged liquid was stirred at 125°C, and a monomer mixture consisting of 30 parts of γ-methacryloxypropyltrimethoxysilane, 35 parts of 2-hydroxypropyl acrylate, 20 parts of styrene, 15 parts of isobutyl methacrylate, and 1.5 parts of 2,2'-azobis(2-methylbutyronitrile) (polymerization initiator) was dropped therein at a uniform rate over 4 hours. After aging at 125°C for 30 minutes, a solution consisting of 0.5 parts of 2,2'-azobis(2-methylbutyronitrile) and 5.0 parts of "Swasol 1000" was dropped therein at a uniform rate over 1 hour. After aging at 125°C for 1 hour, the mixture was cooled and diluted by adding 6 parts of isobutyl acetate to obtain an acrylic resin solution having a hydroxyl group and an alkoxysilyl group with a solid content concentration of 65% by mass. The obtained acrylic resin having a hydroxyl group and an alkoxysilyl group had an alkoxysilyl group content of 1.2 mmol / g, a hydroxyl value of 151 mgKOH / g, a weight average molecular weight of 7000, and a glass transition temperature of 16.6°C.

[0226] Production of hydroxyl-containing polyester resin

[0227] Production Example 3

[0228] 100.1 parts of hexahydrophthalic anhydride and 118 parts of 1,6-hexanediol were charged into a reactor equipped with a stirrer, a reflux condenser, a water separator and a thermometer, and reacted at 230°C for 6 hours, and then diluted with butyl acetate to obtain a hydroxyl-containing polyester resin solution having a solid content concentration of 80%. The obtained hydroxyl-containing polyester resin had an acid value of 2 mgKOH / g, a hydroxyl value of 192 mgKOH / g, and a number average molecular weight of 578.

[0229] Production of hydroxyl-containing non-aqueous dispersion type acrylic resin

[0230] Production Example 4

[0231] Into a four-necked flask equipped with a stirrer, a thermometer, a condenser, and a nitrogen inlet, 93 parts of heptane and 98 parts of the following 55% polymer dispersion stabilizer solution (※1) were placed, heated to reflux, and a mixture of the following monomers and a polymerization initiator was added dropwise over 3 hours, and further aged for 2 hours, thereby obtaining a hydroxyl-containing non-aqueous dispersion type acrylic resin.

[0232] (Mixture of monomer and polymerization initiator)

[0233] A mixture of 15 parts of styrene, 40 parts of methyl methacrylate, 30 parts of acrylonitrile, 15 parts of 2-hydroxyethyl methacrylate and 1.5 parts of tert-butyl peroxy-2-ethylhexanoate.

[0234] The obtained non-aqueous dispersion type acrylic resin was a milky white stable low-viscosity polymer dispersion having a mass solid content concentration of 53%, a Gardner viscosity B, and an average particle size (measured by electron microscope) of 0.2 to 0.3 μm.

[0235] (Synthesis of polymer dispersion stabilizer solution (※1))

[0236] Into a four-necked flask equipped with a stirring device, a thermometer, a condenser and a nitrogen inlet, 40 parts of isobutyl acetate and 40 parts of toluene were charged, heated to reflux, and a mixture of the following monomers and a polymerization initiator was added dropwise over 3 hours. After the addition, the mixture was aged for 2 hours to obtain a polymer dispersion stabilizer solution.

[0237] (Mixture of monomer and polymerization initiator)

[0238] A mixture of 10 parts of styrene, 49 parts of isobutyl methacrylate, 30 parts of 2-ethylhexyl methacrylate, 11 parts of 2-hydroxyethyl methacrylate and 2 parts of azobisisobutyronitrile.

[0239] Production of coating compositions

[0240] Embodiment 18

[0241] The following components were blended: 5 parts (solid content 2 parts) of the acrylic resin-modified silica particles (AB-1) obtained in Example 1, 75.4 parts (solid content 49 parts) of the hydroxyl-containing acrylic resin obtained in Preparation Example 1, 12.5 parts (solid content 10 parts) of the hydroxyl-containing polyester resin obtained in Preparation Example 3, 3.8 parts (solid content 2 parts) of the hydroxyl-containing non-aqueous dispersion type acrylic resin obtained in Preparation Example 4, 39 parts (solid content 39 parts) of "Sumidur N3300" (trade name, manufactured by Sumika Covestro Urethane Co., Ltd., isocyanurate cycloadduct of hexamethylene diisocyanate, solid content 100%), 1.2 parts (solid content 0.3 parts) of "NACURE 4167" (trade name, manufactured by KING INDUSTRIES Co., Ltd., triethylamine salt of alkylphosphoric acid, curing catalyst, active ingredient 25%), and 1.2 parts (solid content 0.3 parts) of "SETALUX 61767VX-60" (trade name, manufactured by Allnex, viscosity adjuster, solid content 60%) 0.5 parts (solid content 0.3 parts), "LHP-96" (trade name, manufactured by Kusumoto Chemicals, surface adjuster, active ingredient 50%) 0.2 parts (solid content 0.1 parts), "TINUVIN 400" (trade name, manufactured by BASF, benzotriazole-based ultraviolet absorber, active ingredient 100%) 2 parts (solid content 2 parts) and "HOSTAVIN 3058" (trade name, manufactured by Clarion, hindered amine-based light stabilizer, acylated hindered amine, active ingredient 100%) 4 parts (solid content 4 parts) were diluted with butyl acetate and stirred in a manner such that the solid content of the coating became 52%, thereby obtaining coating composition No. 1.

[0242] Examples 19 to 46, Comparative Examples 3 to 6

[0243] Coating compositions Nos. 2 to 33 were obtained in the same manner as in Example 18 except that the formulations shown in Tables 4 to 8 were used.

[0244] It should be noted that (Note 5) to (Note 7) in the table have the following meanings.

[0245] (Note 5) "Desmodur N3900": a trade name, manufactured by Sumika Covestro Urethane Co., Ltd., a polyisocyanate compound of hexamethylene diisocyanate.

[0246] (Note 6) "Cymel 250": trade name, manufactured by Allnex Japan Co., Ltd., methyl butyl mixed etherified melamine resin.

[0247] (Note 7) “DISPARLON NSH8430”: Trade name, manufactured by Kusumoto Chemicals Co., Ltd., silicone-modified acrylic acid.

[0248] Preparation of coated panels for testing

[0249] On a 0.8 mm thick matte steel plate subjected to zinc phosphate chemical treatment, "ELECRON GT-10" (trade name, manufactured by KANSAIPAINT, a heat-curable epoxy resin-based cationic electrodeposition paint) was electrostatically coated to a film thickness of 20 μm, and cured by heating at 170°C for 30 minutes. Then, "WP-523H" (trade name, manufactured by KANSAIPAINT, an acrylic / melamine resin-based water-based mid-coat composition) was electrostatically coated to a cured film thickness of 20 μm using a rotary atomization type electrostatic coating machine, and left for 5 minutes to form an uncured mid-coat film. On the uncured mid-coat film, a water-based base coat "WBC713T" (trade name, manufactured by KANSAIPAINT, an acrylic / melamine resin-based automotive top coat base coat paint, black color) was applied to a dry film thickness of 15 μm, left at room temperature for 5 minutes, and then preheated at 80°C for 5 minutes to form an uncured base coat film. Next, each coating composition obtained in the above-mentioned embodiment and comparative example was applied to the uncured primer coating film in a manner to a film thickness of 35 μm, left at room temperature for 10 minutes, and then heated at 140° C. for 30 minutes to cure, thereby obtaining a test coated plate. Each obtained test coated plate was left at room temperature for 7 days, and then the following coating performance test was performed. The evaluation results are shown in Tables 4 to 8.

[0250] Scratch resistance

[0251] For each test coated plate obtained above, a Gakushin type friction tester (SDL ATLAS, CrockMeter M238BB CM-5) was used to reciprocate 10 times. The abrasive used at this time was "wet or dry polishing pad 281Q particle size 9μm" (trade name, 3M company, abrasive). After the test, the coating surface was air-sprayed, and the 20° gloss before and after the test was measured using a gloss meter (Byk-Gardner company, device name: micro-TRI-gloss), and the gloss retention rate was calculated according to the following formula. S, A and B are qualified levels.

[0252] Gloss after test / initial gloss × 100

[0253] S: more than 85%,

[0254] A: 80% or more and less than 85%,

[0255] B: 65% or more and less than 80%,

[0256] C: 50% or more and less than 65%,

[0257] D: Less than 50%.

[0258] Recoat Adhesion

[0259] The water-based primer "WBC713T" (manufactured by KANSAIPAINT, trade name, acrylic / melamine resin automotive topcoat paint, black color) was re-coated on each test coated plate obtained above so that the film thickness became 15 μm, and then left at room temperature for 5 minutes, and preheated at 80° C. for 5 minutes to form an uncured primer coating film. Next, each coating composition obtained in the above examples and comparative examples was applied on the uncured primer coating film so that the film thickness became 35 μm, left at room temperature for 10 minutes, and then heated at 140° C. for 30 minutes to cure, thereby obtaining a coated plate for a recoat adhesion test.

[0260] The recoat adhesion of each coated plate obtained for recoat adhesion test was tested by a square grid (100 square grids of 2 mm×2 mm in size) adhesive transparent tape peeling test described in JIS K5600 and evaluated according to the following criteria: S, A, and B are pass levels.

[0261] S: The number of remaining squares is 100.

[0262] A: The number of squares remaining is 99 to 90.

[0263] B: The number of squares remaining is 89 to 70.

[0264] C: The number of squares remaining is between 69 and 35.

[0265] D: The number of remaining squares is 34 or less.

[0266] Transparency

[0267] Based on the L measured by "CM-512m3" (trade name, manufactured by Konica Minolta, multi-angle spectrophotometer) * The transparency of each test coated plate obtained above was evaluated by L * The values ​​are the L values ​​when the standard light D65 is irradiated from three angles: 25° (highlight direction), 45°, and 75° (shadow direction) with respect to the receiving angle (the direction perpendicular to the coating surface is set to 0°). * The total value of the value. *The smaller the value, the brighter the black color of the base coat film underneath appears, indicating that the transparency of the formed clear coat film is higher. S, A, and B are passing levels.

[0268] S:L * The sum of the values ​​is less than 1.5,

[0269] A: L * The sum of the values ​​is greater than 1.5 and less than 2.0,

[0270] B:L * The sum of the values ​​is greater than 2.0 and less than 2.5,

[0271] C:L * The total of the values ​​is greater than 2.5 and less than 3.5,

[0272] D:L * The total of the values ​​is 3.5 or more.

[0273] [Table 4]

[0274]

[0275] [Table 5]

[0276]

[0277] [Table 6]

[0278]

[0279] [Table 7]

[0280]

[0281] [Table 8]

[0282]

[0283] As mentioned above, although embodiment and Example of this invention were specifically described, this invention is not limited to the said embodiment, Various deformation|transformation based on the technical idea of ​​this invention is possible.

Claims

1. An acrylic resin-modified silica particle, comprising silica particles (A) and an acrylic resin (B) bonded to the silica particles (A), wherein the acrylic resin (B) has at least one chain selected from a polyoxyalkylene chain and a polyester chain and a polysiloxane structure, The acrylic resin modified silica particles are the reaction product of silica particles (a1) and compound (a2), The silica particles (a1) are bonded to an acrylic resin having a first chemically reactive group, The silica particles (a1) bonded to the acrylic resin having a first chemically reactive group are the reaction product of silica particles (a11) having a polymerizable unsaturated group and a polymerizable unsaturated monomer mixture (a12), wherein the polymerizable unsaturated monomer mixture (a12) contains a polymerizable unsaturated monomer (a121) having a first chemically reactive group as at least a part of its components.

2. The acrylic resin-modified silica particles according to claim 1, wherein The silica particles (A) are colloidal silica having an average primary particle size of 5 to 100 nm.

3. The acrylic resin-modified silica particles according to claim 1 or 2, wherein The compound (a2) has a second chemically reactive group capable of reacting with the first chemically reactive group, at least one chain selected from a polyoxyalkylene chain and a polyester chain, and a polysiloxane structure.

4. The acrylic resin-modified silica particles according to claim 1, wherein The polymerizable unsaturated monomer (a121) having a first chemically reactive group is at least one polymerizable unsaturated monomer selected from a carboxyl-containing polymerizable unsaturated monomer, an epoxy-containing polymerizable unsaturated monomer, an isocyanate-containing polymerizable unsaturated monomer, and an amino-containing polymerizable unsaturated monomer.

5. The acrylic resin-modified silica particles according to claim 3, wherein The compound (a2) having a second chemically reactive group capable of reacting with the first chemically reactive group, at least one chain selected from a polyoxyalkylene chain and a polyester chain, and a polysiloxane structure is a compound having at least one chemically reactive group selected from an epoxy group, a carboxyl group, an amino group, a hydroxyl group and an isocyanate group as the second chemically reactive group.

6. The acrylic resin-modified silica particles according to claim 3, wherein The number average molecular weight of the compound (a2) having the second chemically reactive group capable of reacting with the first chemically reactive group, at least one chain selected from a polyoxyalkylene chain and a polyester chain, and a polysiloxane structure is within a range of 200 to 4,000.

7. The acrylic resin-modified silica particles according to claim 3, wherein The mass ratio of the silica particles (a1) to the compound (a2) is in the range of (a1) / (a2)=90 / 10 to 98 / 2, the compound (a2) has a second chemically reactive group capable of reacting with the first chemically reactive group, at least one chain selected from a polyoxyalkylene chain and a polyester chain, and a polysiloxane structure, and the silica particles (a1) are bonded to an acrylic resin having a first chemically reactive group.

8. The acrylic resin-modified silica particles according to claim 1 or 2, wherein The acrylic resin (B) having at least one chain selected from a polyoxyalkylene chain and a polyester chain and a polysiloxane structure is an acrylic resin (B′) further having a hydroxyl group.

9. The acrylic resin-modified silica particles according to claim 1, wherein The acrylic resin (B) having at least one chain selected from a polyoxyalkylene chain and a polyester chain and a polysiloxane structure is an acrylic resin (B') further having a hydroxyl group, and the hydroxyl value of the acrylic resin produced from the polymerizable unsaturated monomer mixture (a12) is in the range of 60 to 140 mgKOH / g.

10. The acrylic resin-modified silica particles according to claim 1 or 2, wherein In the acrylic resin-modified silica particles, the mass ratio of the polysiloxane structure to the at least one chain selected from polyoxyalkylene chains and polyester chains is in the range of 65 / 35 to 5 / 95 in terms of mass ratio of polysiloxane structure / at least one chain selected from polyoxyalkylene chains and polyester chains.

11. The acrylic resin-modified silica particles according to claim 1, wherein The silica particles (A) are prepared using silica particles (a1) bonded to an acrylic resin, which are obtained by reacting silica particles (a11) having a polymerizable unsaturated group with a polymerizable unsaturated monomer mixture (a12) containing a polymerizable unsaturated monomer (a121). 12 . A coating composition comprising the acrylic resin-modified silica particles according to claim 1 and a binder component.

13. The coating composition according to claim 12, wherein The binder component includes a hydroxyl-containing resin and a crosslinking agent.

14. A method for forming a multilayer coating film, wherein the multilayer coating film is formed by sequentially coating at least one layer of a colored base coating paint and at least one layer of a clear coating paint on a coated object, wherein: The method comprises the step of applying the coating composition according to claim 12 or 13 as an uppermost clear coating layer.

Citation Information

Patent Citations

  • Coating composition, and method for forming coated film

    JP2013053305A

  • Coating composition and coated article

    JP2013249400A

  • Hydrophilic coating agent, hydrophilic coating film and hydrophilic base

    CN101910334A